A genome-wide association study with tissue transcriptomics identifies genetic drivers for classic bladder exstrophy - Mingardo, Enrico; Beaman, Glenda; Grote, Philip; Nordenskjöld, Agneta; Newman, William; Woolf, Adrian S.; Eckstein, Markus; Hilger, Alina C.; Dworschak, Gabriel C.; Rösch, Wolfgang; Ebert, Anne Karolin; Stein, Raimund; et al. (Communications Biology, 2022)
Classic bladder exstrophy represents the most severe end of all human congenital anomalies of the kidney and urinary tract and is associated with bladder cancer susceptibility. Previous genetic studies identified one locus to be involved in classic bladder exstrophy, but were limited to a restrict number of cohort. Here we show the largest classic bladder exstrophy genome-wide association analysis to date where we identify eight genome-wide significant loci, seven of which are novel. In these regions reside ten coding and four non-coding genes. Among the coding genes is EFNA1, strongly expressed in mouse embryonic genital tubercle, urethra, and primitive bladder. Re-sequence of EFNA1 in the investigated classic bladder exstrophy cohort of our study displays an enrichment of rare protein altering variants. We show that all coding genes are expressed and/or significantly regulated in both mouse and human embryonic developmental bladder stages. Furthermore, nine of the coding genes residing in the regions of genome-wide significance are differentially expressed in bladder cancers. Our data suggest genetic drivers for classic bladder exstrophy, as well as a possible role for these drivers to relevant bladder cancer susceptibility.
CRIS-Team Scopus Importer:2022-11-25

Anorectal malformations - de Blaauw, Ivo; Stenström, Pernilla; Yamataka, Atsuyuki; Miyake, Yuichiro; Reutter, Heiko Martin; Midrio, Paola; Wood, Richard; Grano, Caterina; Pakarinen, Mikko (Nature Reviews Disease Primers, 2024)
Anorectal malformations (ARM) are rare congenital anomalies with an overall prevalence of 3.32 per 10,000 pregnancies. ARM describe a spectrum of anomalies of the anus and rectum ranging from a minimally displaced anal canal to a complete fusion of the anorectum, vagina and urethra with hypoplastic sphincter and pelvic floor muscle. Aberrant septation of the hindgut with anomalous cloacal membrane during weeks 6 to 9 of gestation form the developmental basis for a spectrum of anomalies defined as ARM. Although underlying specific syndromes and occasional familiar occurrence suggest genetic aetiology, most ARM are non-syndromic and their causal genetic mechanisms and non-genetic insults remain unclear. ARM is a clinical diagnosis, generally made early after birth via careful inspection of the perineum. Prenatal detection remains rare, and modern technical developments have added little to prenatal diagnostics. ARM is corrected surgically. Since its introduction in 1982, posterior sagittal anorectoplasty is the most common surgery for ARM reconstruction. Subsequent surgical adaptations focus on minimizing iatrogenic operative injury by limiting surgical invasiveness. They include laparoscopic procedures and shortening of incisions with confined dissection in open surgery. Although outcomes in patients with ARM have evolved throughout the past decades, there is urgent need for further improvements both in functional outcomes and quality of life. The importance of psychosocial experiences of affected patients is increasingly recognized. Continued research is necessary to improve prenatal detection, to elucidate genetic and epigenetic alterations and to refine optimal surgical procedures.
CRIS-Team Scopus Importer:2024-11-29

Application of Next-Generation Sequencing to Enterobacter Hormaechei Subspecies Analysis during a Neonatal Intensive Care Unit Outbreak - Morhart, Patrick; Gerlach, Roman; Kunz, Caroline; Held, Jürgen; Valenza, Giuseppe; Wölfle, Joachim; Reutter, Heiko Martin; Hanslik, Gregor J.; Fahlbusch, Fabian B. (Children, 2023)
Introduction: The Enterobacter cloacae complex (ECC) species are potential neonatal pathogens, and ECC strains are among the most commonly encountered Enterobacter spp. associated with nosocomial bloodstream infections. Outbreaks caused by ECC can lead to significant morbidity and mortality in susceptible neonates. At the molecular level, ECC exhibits genomic heterogeneity, with six closely related species and subspecies. Genetic variability poses a challenge in accurately identifying outbreaks by determining the clonality of ECC isolates. This difficulty is further compounded by the limitations of the commonly used molecular typing methods, such as pulsed field gel electrophoresis, which do not provide reliable accuracy in distinguishing between ECC strains and can lead to incorrect conclusions. Next-generation sequencing (NGS) offers superior resolution in determining strain relatedness. Therefore, we investigated the clinical pertinence of incorporating NGS into existing bundle measures to enhance patient management during an outbreak of ECC in a level-3 neonatal intensive care unit (NICU) in Germany. Methods: As the standard of care, all neonates on the NICU received weekly microbiological swabs (nasopharyngeal and rectal) and analysis of endotracheal secretion, where feasible. During the 2.5-month outbreak, colonisation with ECC was detected in n = 10 neonates. The phylogenetic relationship and potential antimicrobial resistance genes as well as mobile genetic elements were identified via bacterial whole-genome sequencing (WGS) using Illumina MiSeq followed by in silico data analysis. Results: Although all ECC isolates exhibited almost identical antimicrobial susceptibility patterns, the WGS data revealed the involvement of four different ECC clones. The isolates could be characterised as Enterobacter hormaechei subspecies steigerwaltii (n = 6, clonal), subsp. hoffmannii (n = 3, two clones) and subsp. oharae (n = 1). Despite the collection of environmental samples, no source of this diffuse outbreak could be identified. A new standardised operating procedure was implemented to enhance the management of neonates colonised with MRGN. This collaborative approach involved both parents and medical professionals and successfully prevented further transmission of ECC. Conclusions: Initially, it was believed that the NICU outbreak was caused by a single ECC clone due to the similarity in antibiotic resistance. However, our findings show that antibiotic susceptibility patterns can be misleading in investigating outbreaks of multi-drug-resistant ECC. In contrast, bacterial WGS accurately identified ECC at the clonal level, which significantly helped to delineate the nature of the observed outbreak.
CRIS-Team Scopus Importer:2023-11-03
Keywords: ECC; Enterobacter; MRGN; NGS; NICU; WGS

A Prevalence Estimation of Exstrophy and Epispadias in Germany From Public Health Insurance Data - Ebert, Anne Karoline; Zwink, Nadine; Reutter, Heiko Martin; Jenetzky, Ekkehart (Frontiers in Pediatrics, 2021)
Introduction: The prevalence of rare diseases is very important for health care research. According to the European Surveillance of Congenital Anomalies (EUROCAT) registers, the live prevalence for exstrophy and/or epispadias (grades 1–3) is reported with 1:23,255 (95% CI: 1:26,316; 1:20,000). A Europe-wide prevalence evaluation based on reports from excellence centers estimates a prevalence for exstrophies of 1:32,200 and for isolated epispadias of 1:96,800 in 2010. However, the frequency of exstrophy [International Statistical Classification of Diseases and Related Health Problems revision 10 (ICD-10): Q64.1] and epispadias (ICD-10: Q64.0) treated in different age groups in Germany remains unclear. Material and Method: Public health insurance data from 71 million people (approximately 87% of the population) were provided by the German Institute for Medical Documentation and Information (DIMDI) in accordance to the German Social Insurance Code for this research purpose. DIMDI analyzed the data source for the ICD diagnoses exstrophy and epispadias between 2009 and 2011. As provided data were robust over the years, averaged data are mentioned. Detailed subgroup analysis of small numbers was forbidden due to privacy protection. Results: Annually, 126 persons of all ages with epispadias and 244 with exstrophy are treated as inpatients. In the observed population, 34 infants (<1 year of age) with epispadias and 19 with exstrophy (58% male) are treated as outpatients each year. This corresponds to an estimated live prevalence of 1:11,000 (95% CI: 1:14,700; 1:8,400) for EEC (exstrophy–epispadias complex), more specifically a prevalence of 1:17,142 for epispadias and of 1:30,675 for exstrophy. The male-to-female ratio for exstrophy is 1.4:1 for infants and 1.6:1 for all minors. In children and adolescents, 349 epispadias and 393 exstrophies (up to the age of 17) are treated annually, whereas adults with exstrophy and even more with epispadias make comparatively less use of medical care. Conclusion: With the help of DIMDI data, the live prevalence of bladder exstrophy and epispadias in Germany could be estimated. The prevalence of epispadias was higher than in previous reports, in which milder epispadias phenotypes (grade 1 or 2) may not have been included. These analyses might enlighten knowledge about nationwide incidence and treatment numbers of rare diseases such as the EEC.
CRIS-Team Scopus Importer:2021-11-19
Keywords: bladder exstrophy; bladder exstrophy epispadias complex (EEC); epispadias; health insurance; prevalence; public health

A Quality Assessment of the ARM-Net Registry Design and Data Collection. - Hageman, Isabel C.; van der Steeg, Hendrik J.J.; Jenetzky, Ekkehart; Trajanovska, Misel; King, Sebastian K.; de Blaauw, Ivo; van Rooij, Iris A.L.M.; Aminoff, Dalia; Amerstorfer, Eva; Till, Holger; Bagolan, Piero; Iacobelli, Barbara; et al. (Journal of Pediatric Surgery, 2023)
BACKGROUND: Registries are important in rare disease research. The Anorectal Malformation Network (ARM-Net) registry is a well-established European patient registry collecting demographic, clinical, and functional outcome data. We assessed the quality of this registry through review of the structure, data elements, collected data, and user experience. MATERIAL AND METHODS: Design and data elements were assessed for completeness, consistency, usefulness, accuracy, validity, and comparability. An intra- and inter-user variability study was conducted through monitoring and re-registration of patients. User experience was assessed via a questionnaire on registration, design of registry, and satisfaction. RESULTS: We evaluated 119 data elements, of which 107 were utilized and comprised 42 string and 65 numeric elements. A minority (37.0%) of the 2278 included records had complete data, though this improved to 83.5% when follow-up elements were excluded. Intra-observer variability demonstrated 11.7% incongruence, while inter-observer variability was 14.7%. Users were predominantly pediatric surgeons and typically registered patients within 11-30 min. Users did not experience any significant difficulties with data entry and were generally satisfied with the registry, but preferred more longitudinal data and patient-reported outcomes. CONCLUSIONS: The ARM-Net registry presents one of the largest ARM cohorts. Although its collected data are valuable, they are susceptible to error and user variability. Continuous evaluations are required to maintain relevant and high-quality data and to achieve long-term sustainability. With the recommendations resulting from this study, we call for rare disease patient registries to take example and aim to continuously improve their data quality to enhance the small, but impactful, field of rare disease research. LEVEL OF EVIDENCE: V.
EVALuna2:548069

Association Between Exstrophy-epispadias Complex And Congenital Anomalies: A German Multicenter Study - Ebert, Anne Karoline; Zwink, Nadine; Jenetzky, Ekkehart; Stein, Raimund; Boemers, Thomas M.; Lacher, Martin; Fortmann, Caroline; Obermayr, Florian; Fisch, Margit; Mortazawi, Kiarasch; Schmiedeke, Eberhard; Eisenschmidt, Volker; et al. (Urology, 2019)
Objective: To further investigate associated anomalies in exstrophy-epispadias complex (EEC) patients congenital uro-rectal malformations network (CURE-Net) database was systematically screened. In literature the EEC comprises a spectrum of anomalies, mainly occurring “isolated” without additional congenital defects. Nevertheless, previous epidemiological studies indicated a higher association with renal, anorectal, and lower neurotubular anomalies, which may originate from the same developmental morphogenetic fields. Materials and Methods: Seventy-three prospectively (born since 2009) and 162 cross-sectional recruited EEC patients (born 1948-2008) were analyzed. Associated anomalies were derived from patient's medical data as well as from a physical examination during a physician's interview, classified according to the international statistical classification of diseases and related health problems and grouped with the London Dysmorphology Database. Descriptive statistical analyses were performed. Results: Majority of participants were male (68%) and expressed the classical bladder exstrophy phenotype (71%). Exstrophy variants occurred significantly more often in newborns (21%, P <.0001). Anomalies such as inguinal hernias, skeleton, and joint anomalies were equally present in both groups (P =.65 and P =.67). Heart defects were seen more often in newborns (6%) than in the cross-sectional group (1%; P =.033) and the general German population (1%). In total, 59% of the prospective and 48% of the cross-sectional patients had associated anomalies outside the spectrum (P =.16). Conclusion: Phenomenological multicenter data confirmed the dimension of associated anomalies inside and outside the EEC spectrum. The detected anomalies are either important in preparing for the primary reconstruction or later in long-term follow-up. Associated anomalies of EEC should be spotlighted during routine check-up in all EEC patients.
CRIS-Team Scopus Importer:2019-06-04

Ätiologische Konzepte von gastrointestinalen Fehlbildungen/Atresien - Reutter, Heiko Martin (Monatsschrift Kinderheilkunde, 2023)
The causes of gastrointestinal malformations or atresias are heterogeneous. Most atresias occur sporadically. To date, no environmental factor or genetic defect has been identified that alone could causally explain a large proportion of the various malformations. Due to the capabilities of modern array and exome analyses, numerous new disease genes have been identified in the past 10 years. It is known that a small overlap of individual causative genetic risk factors underlies the co-occurrence of malformations of the esophagus and anorectum, and that a large proportion of duodenal atresias occur in the context of an underlying Down syndrome; however, for the vast majority of intestinal atresias the genetic causes remain unclear. The human genetic counselling should consider epidemiological aspects of the observed recurrence risk for the different atresias and the appearance of each atresia (syndromic or non-syndromic, isolated).
CRIS-Team Scopus Importer:2023-05-19
Keywords: Chromosome disorders; DNA copy number variations; Epidemiology; Pathogenesis; Recurrence risk

Blood pressure and kidney function in neonates and young infants with intrauterine growth restriction - Heuchel, Katharina Monika; Ebach, Fabian; Alsat, Ebru Aileen; Reutter, Heiko Martin; Mueller, Andreas; Hilger, Alina Christine (Pediatric Nephrology, 2022)
Background: Intrauterine growth restriction (IUGR) has been associated with changes in kidney anatomy, nephrogenesis and the vascular system, resulting in secondary arterial hypertension and kidney damage in adulthood. Here, we compare routine clinical and metabolic parameters between IUGR and non-IUGR study participants in the neonatal and early infant period. Methods: A total of 39 IUGR and 60 non-IUGR neonates were included during an 18-month study period. We compared blood pressure, serum creatinine (SCr), urea nitrogen (BUN), urinary albumin, α-1-microglobulin, transferrin, immunoglobulin G and total protein excretion in spontaneous urine normalized by urine creatinine level during the hospital stay. Results: There were no significant differences in mean values of blood pressure and urinary protein excretion between cases and controls. SCr and BUN levels were lower in the IUGR group compared to the non-IUGR group. Conclusions: The lower levels of SCr and BUN may be attributed to lower liver and muscle mass in IUGR neonates and young infants. Biomarkers currently used in routine clinical care do not allow early postnatal prediction of higher blood pressure or worse kidney function due to IUGR, so further studies are needed. Graphical abstract: A higher resolution version of the Graphical abstract is available as Supplementary information. [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2022-09-16
Keywords: Blood pressure; Intrauterine growth restriction; Kidney function; Neonates; Proteinuria

Brain Abnormalities in Patients with Germline Variants in H3F3: Novel Imaging Findings and Neurologic Symptoms Beyond Somatic Variants and Brain Tumors - Alves, C. A.P.F.; Sherbini, O.; D’Arco, F.; Steel, D.; Kurian, M. A.; Radio, F. C.; Ferrero, G. B.; Carli, D.; Tartaglia, M.; Balci, T. B.; Powell-Hamilton, N. N.; Schrier Vergano, S. A.; et al. (American Journal of Neuroradiology, 2022)
BACKGROUND AND PURPOSE: Pathogenic somatic variants affecting the genes Histone 3 Family 3A and 3B (H3F3) are extensively linked to the process of oncogenesis, in particular related to central nervous system tumors in children. Recently, H3F3 germline missense variants were described as the cause of a novel pediatric neurodevelopmental disorder. We aimed to investigate patterns of brain MR imaging of individuals carrying H3F3 germline variants. MATERIALS AND METHODS: In this retrospective study, we included individuals with proved H3F3 causative genetic variants and available brain MR imaging scans. Clinical and demographic data were retrieved from available medical records. Molecular genetic testing results were classified using the American College of Medical Genetics criteria for variant curation. Brain MR imaging abnormalities were analyzed according to their location, signal intensity, and associated clinical symptoms. Numeric variables were described according to their distribution, with median and interquartile range. RESULTS: Eighteen individuals (10 males, 56%) with H3F3 germline variants were included. Thirteen of 18 individuals (72%) presented with a small posterior fossa. Six individuals (33%) presented with reduced size and an internal rotational appearance of the heads of the caudate nuclei along with an enlarged and squared appearance of the frontal horns of the lateral ventricles. Five individuals (28%) presented with dysgenesis of the splenium of the corpus callosum. Cortical developmental abnormalities were noted in 8 individuals (44%), with dysgyria and hypoplastic temporal poles being the most frequent presentation. CONCLUSIONS: Imaging phenotypes in germline H3F3-affected individuals are related to brain features, including a small posterior fossa as well as dysgenesis of the corpus callosum, cortical developmental abnormalities, and deformity of lateral ventricles.
CRIS-Team Scopus Importer:2022-08-19

Centralization as the key survival benefit in acute neonatal surgery - Besendörfer, Manuel; Günster, Simone; Linz, Katja; Reutter, Heiko Martin; Diez, Sonja (Frontiers in Pediatrics, 2024)
Introduction: Centralization of neonatal surgical care for congenital malformations is already under discussion. Acute care of neonatal emergencies in perinatal centers with affiliated hospitals is not uniformly regulated in Germany. Materials and methods: Analyses are based on acute pediatric surgical care at four affiliated hospitals of a perinatal center. Epidemiologic data and outcome parameters “survival”, “intracerebral hemorrhage”, and “revision of surgical indication” are assessed. Comparison is made between patients receiving surgical treatment at affiliated hospitals (group A) and patients with transfer to the university center for therapy in case of surgical indication for gastrointestinal diseases (group B). Results: 17 group A-patients are compared to 40 group B-patients. Comparison of epidemiological data reveals no significant differences. There is a survival advantage with transfer to the university center (mortality of 29% in group A vs. 2% in group B, p = 0.007). Intracerebral hemorrhage occurred more frequently in externally treated patients (group A 24% vs. group B 2%, p = 0.024). Surgical indication was revised in 30% of group B at the university center (p = 0.011) with consecutive successful conservative treatment. Conclusion: Transfer of patients at the beginning of the acute phase of gastrointestinal diseases is key to optimize the quality of neonatal surgical care. However, larger population studies should confirm the presented results, discuss restricting factors of real care structures and should rule out bias in triage of patients.
CRIS-Team Scopus Importer:2024-04-05
Keywords: centralization; German medical system; neonatal emergency; neonatal surgery; perinatal center

Common variants increase risk for congenital diaphragmatic hernia within the context of de novo variants - Qiao, Lu; Welch, Carrie L.; Hernan, Rebecca; Wynn, Julia; Krishnan, Usha S.; Zalieckas, Jill M.; Buchmiller, Terry; Khlevner, Julie; De, Aliva; Farkouh-Karoleski, Christiana; Wagner, Amy J.; Heydweiller, Andreas; et al. (American Journal of Human Genetics, 2024)
Congenital diaphragmatic hernia (CDH) is a severe congenital anomaly often accompanied by other structural anomalies and/or neurobehavioral manifestations. Rare de novo protein-coding variants and copy-number variations contribute to CDH in the population. However, most individuals with CDH remain genetically undiagnosed. Here, we perform integrated de novo and common-variant analyses using 1,469 CDH individuals, including 1,064 child-parent trios and 6,133 ancestry-matched, unaffected controls for the genome-wide association study. We identify candidate CDH variants in 15 genes, including eight novel genes, through deleterious de novo variants. We further identify two genomic loci contributing to CDH risk through common variants with similar effect sizes among Europeans and Latinx. Both loci are in putative transcriptional regulatory regions of developmental patterning genes. Estimated heritability in common variants is ∼19%. Strikingly, there is no significant difference in estimated polygenic risk scores between isolated and complex CDH or between individuals harboring deleterious de novo variants and individuals without these variants. The data support a polygenic model as part of the CDH genetic architecture.
CRIS-Team Scopus Importer:2024-11-08
Keywords: common variants; congenital diaphragmatic hernia; de novo variants; genome-wide association study; single-nucleotide polymorphism; WNT5A

Definition, diagnosis and clinical management of non-obstructive kidney dysplasia: a consensus statement by the ERKNet Working Group on Kidney Malformations - Kohl, Stefan; Avni, Fred E.; Boor, Peter; Capone, Valentina; Clapp, William L.; De Palma, Diego; Harris, Tess; Heidet, Laurence; Hilger, Alina Christine; Liapis, Helen; Lilien, Marc; Manzoni, Gianantonio; et al. (Nephrology Dialysis Transplantation, 2022)
Kidney dysplasia is one of the most frequent causes of chronic kidney failure in children. While dysplasia is a histological diagnosis, the term 'kidney dysplasia' is frequently used in daily clinical life without histopathological confirmation. Clinical parameters of kidney dysplasia have not been clearly defined, leading to imprecise communication amongst healthcare professionals and patients. This lack of consensus hampers precise disease understanding and the development of specific therapies. Based on a structured literature search, we here suggest a common basis for clinical, imaging, genetic, pathological and basic science aspects of non-obstructive kidney dysplasia associated with functional kidney impairment. We propose to accept hallmark sonographic findings as surrogate parameters defining a clinical diagnosis of dysplastic kidneys. We suggest differentiated clinical follow-up plans for children with kidney dysplasia and summarize established monogenic causes for non-obstructive kidney dysplasia. Finally, we point out and discuss research gaps in the field.
CRIS-Team WoS Importer:2022-09-16

Diagnostic Utility of Interleukin-6 in Early-Onset Sepsis among Term Newborns: Impact of Maternal Risk Factors and CRP Evaluation. - Schleier, Maria; Lubig, Julia; Kehl, Sven; Hébert, Steven; Wölfle, Joachim; van der Donk, Adriana; Bär, Alisa; Reutter, Heiko Martin; Hepp, Tobias; Morhart, Patrick (Children, 2023)
(1) Background: Interleukin-6 (IL-6) levels act as an early infection marker preceding C-reactive protein (CRP) elevation. This study seeks to analyze IL-6 behavior in suspected early-onset sepsis (EOS) cases among term newborns, comparing it to that of CRP and evaluating IL-6's diagnostic utility. We also aim to assess the impact of maternal risk factors on EOS in term newborns, quantifying their influence for informed decision making. (2) Methods: The retrospective data analysis included 533 term newborns who were admitted to our hospital because of suspected EOS. IL-6, CRP, and the impact of maternal risk factors were analyzed in the context of EOS using binomial test, Chi-squared test, logistic and linear regression. (3) Results: In the cases of EOS, both IL-6 and CRP were elevated. The increase in CRP can be predicted by the initial increase in IL-6 levels. Among the assessed risk factors, intrapartum maternal fever (adjusted odds ratio 18.1; 95% CI (1.7-4.1)) was identified as the only risk factor significantly associated with EOS. (4) Conclusions: Employing IL-6 as an early infection marker enhanced EOS diagnostic precision due to its detectable early rise. However, caution is required, as elevations in IL-6 and CRP levels do not exclusively indicate EOS. Increased CRP levels in healthy newborns with maternal risk factors may be attributed to dynamics of vaginal labor.
EVALuna2:549522

Diving into the Digital Landscape: Assessing the Quality of Online Information on Neonatal Jaundice for Parents - Baumgartner, Michael; Behr, Anna Lena; Garbe, Anne Christina; Quatember, Christoph; Reutter, Heiko Martin; Wölfle, Joachim; Fahlbusch, Fabian Benedikt; Hanslik, Gregor (Children, 2024)
Background: Hyperbilirubinemia is a common condition in newborns. While mild cases of jaundice are common and typically resolve spontaneously, severe hyperbilirubinemia can lead to serious neurologic complications if left untreated. With the constant adaptation of guidelines, clinical management has significantly improved, and treatment has become routine for pediatricians. However, for parents of affected children, managing the condition is not routine. In today’s digital age, parents often seek additional information by accessing a wide range of medical resources on the internet. While this can be empowering, it also presents challenges, as the quality and accuracy of online medical information can vary widely. Therefore, we analyzed the current quality of information on jaundice found on the internet by parents. Methods: A simulated internet search (using the Google search engine) was conducted from a layperson’s perspective using German (“Neugeborenes Gelbsucht”, “Baby Gelbsucht”) and English (“jaundice newborn”, “jaundice baby”) search terms. Subsequently, the quality of the search results was assessed by two independent neonatologists based on the DISCERN Plus Score, HONcode certification, and the JAMA criteria. Results: Websites targeting non-medical laypersons exhibited significant variability in quality. Notably, the content of English websites was superior to that of websites in the German language. The majority of English sites were predominantly institutional, whereas most German sites were commercially oriented. Conclusions: Although information on jaundice is readily accessible online for non-medical individuals, there were notable differences in quality based on language and significant variability in the quality of information warranting attention from healthcare professionals. Furthermore, German websites providing information on jaundice were often hosted by commercial organizations. We propose that pediatric societies engage in developing and maintaining organization-based medical information to improve online resources for parents.
CRIS-Team Scopus Importer:2024-08-02
Keywords: jaundice; neonatal care; online information

Early postnatal echocardiographic assessment of pulmonary blood flow in newborns with congenital diaphragmatic hernia - Kipfmueller, Florian; Heindel, Katrin; Schroeder, Lukas; Berg, Christoph; Dewald, Oliver; Reutter, Heiko M.; Bartmann, Peter; Mueller, Andreas (Journal of Perinatal Medicine, 2018)
Echocardiography is the most important tool to assess infants with congenital diaphragmatic hernia (CDH) for pulmonary hypertension (PH). The pattern of blood flow in the pulmonary artery [described as time to peak velocity (TPV)/right ventricular ejection time (RVET) ratio] provides distinct information about pulmonary arterial pressure. The aim of our study was to investigate the correlation of TPV/RVET measurements with the most commonly used classification system for PH in CDH newborns and the association of these measurements with outcome parameters. Echocardiographic measurements were obtained in 40 CDH newborns within 6 h of life. The obtained measurements were correlated with the decision for or against extracorporeal membrane oxygenation (ECMO); early mortality; total duration of mechanical ventilation and total duration of oxygen supplementation. The correlation coefficient between severity of PH and TPV/RVET measurements was -0.696 (P<0.001). Using receiver operating characteristic (ROC) analyses the optimal cutoff for TPV/RVET in order to predict the necessity for ECMO or early mortality without ECMO was 0.29 with a sensitivity of 86.7%, a specificity of 68%, a positive predictive value of 61.9% and a negative predictive value of 89.5%. Newborns with a TPV/RVET below the cutoff had a 5.9-fold risk for ECMO or early mortality, a significantly longer duration of mechanical ventilation (13.4 days vs. 7.4 days, P=0.003) and oxygen supplementation (22.4 days vs. 9.0 days, P=0.019), and a lower survival rate (76.2% vs. 100%, P=0.021). TPV/RVET is a feasible parameter to assess PH in CDH newborns with close correlation to outcome parameters.
CRIS-Team Scopus Importer:2022-05-03
Keywords: Acceleration time; congenital diaphragmatic hernia; echocardiography; ECMO; pulmonary hypertension; time to peak velocity

Evaluating the Use of Neonatal Colonization Screening for Empiric Antibiotic Therapy of Sepsis and Pneumonia - Bär, Alisa; Schmitt-Grohé, Sabina; Held, Jürgen; Lubig, Julia; Hanslik, Gregor; Fahlbusch, Fabian; Reutter, Heiko Martin; Wölfle, Joachim; van der Donk, Adriana; Schleier, Maria; Hepp, Tobias; Morhart, Patrick (Antibiotics, 2023)
(1) Background: Since 2013, weekly screening for multidrug-resistant Gram-negative (MDRGN) bacteria has been performed in German neonatal intensive care units (NICU). National guidelines recommend considering these colonization analyses for antibiotic treatment regimens. Our retrospective single center study provides insight into the clinical dichotomy of bacterial colonization and infection rates in neonates. (2) Methods: We analyzed microbiological data of neonates admitted to our tertiary level NICU over nine years. Colonization with MDRGN/Serratia marcescens (SERMA) was compared to microbiological findings in sepsis and pneumonia. (3) Results: We analyzed 917 blood and 1799 tracheal aspirate samples. After applying criteria from the Nosocomial Infection Surveillance for Neonates (NEO-KISS), we included 52 and 55 cases of sepsis and pneumonia, respectively; 19.2% of sepsis patients and 34.5% of pneumonia patients had a prior colonization with MDRGN bacteria or SERMA. In these patients, sepsis was not attributable to MDRGN bacteria yet one SERMA, while in pneumonias, ten MDRGN bacteria and one SERMA were identified. We identified late-onset pneumonia and cesarean section as risk factors for MDRGN/SERMA acquisition. (4) Conclusions: Colonization screening is a useful tool for hygiene surveillance. However, our data suggest that consideration of colonization with MDRGN/SERMA might promote extensive use of last resort antibiotics in neonates.
CRIS-Team Scopus Importer:2023-03-10
Keywords: colonization; MDR; MDRGN; multidrug-resistant bacteria; multidrug-resistant Gram-negative bacteria; neonatal infection; neonates; pneumonia; screening; sepsis

Exome sequencing implicates a novel heterozygous missense variant in DSTYK in autosomal dominant lower urinary tract dysfunction and mild hereditary spastic paraparesis. - Vidic, Clara; Zaniew, Marcin; Jurga, Szymon; Thiele, Holger; Reutter, Heiko Martin; Hilger, Alina C. (Molecular and Cellular Pediatrics, 2021)
INTRODUCTION: DSTYK encodes dual serine/threonine and tyrosine protein kinase. DSTYK has been associated with autosomal-dominant congenital anomalies of the kidney and urinary tract and with autosomal-recessive hereditary spastic paraplegia type 23. Here, we report a father and his two dizygotic twin sons carrying a novel heterozygous missense variant in DSTYK, presenting with early onset lower urinary tract dysfunction due to dysfunctional voiding. Moreover, in the later course of the disease, both sons presented with bilateral spasticity in their lower limbs, brisk reflexes, and absence seizures. MATERIALS AND METHODS: Exome sequencing in the affected father and his affected sons was performed. The sons presented clinically with urinary hesitancy, dysfunctional voiding, and night incontinence till adolescence, while the father reported difficulty in voiding. In the sons, cystoscopy excluded urethral valves and revealed hypertrophy of the bladder neck and trabeculated bladder. Additionally, both sons were diagnosed with absence epilepsy in early childhood. Filtering of exome data focused on rare (MAF < 0.01%), autosomal-dominant variants, predicted to be deleterious, residing in highly conserved regions of the exome. RESULTS: Exome analysis identified a novel, heterozygous missense variant (c.271C>A (p.Leu91Met)) in DSTYK segregating with the disease. In silico prediction analyses uniformly rated the variant to be deleterious suggesting the variant to be disease-causing in the family. CONCLUSION: To the best of our knowledge, this is the first report of early onset dysfunctional voiding, seizures, and bilateral spasticity of the lower limbs associated with a novel heterozygous dominant missense variant in DSTYK.
EVALuna2:490519
Keywords: DSTYK; Functional urinary bladder disturbance; HSP23; Hereditary spastic paraparesis; Epilepsy; CAKUT

Exome sequencing in individuals with cardiovascular laterality defects identifies potential candidate genes - Breuer, Katinka; Riedhammer, Korbinian M.; Mueller, Nicole; Schaidinger, Birthe; Dombrowsky, Gregor; Dittrich, Sven; Zeidler, Susanne; Bauer, Ulrike M. M.; Westphal, Dominik S.; Meitinger, Thomas; Dakal, Tikam Chand; Hitz, Marc-Phillip; et al. (European journal of human genetics, 2022)
The birth prevalence of laterality defects is about 1.1/10,000 comprising different phenotypes ranging from situs inversus totalis to heterotaxy, mostly associated with complex congenital heart defects (CHD) and situs abnormalities such as intestinal malrotation, biliary atresia, asplenia, or polysplenia. A proportion of laterality defects arise in the context of primary ciliary dyskinesia (PCD) accompanied by respiratory symptoms or infertility. In this study, exome sequencing (ES) was performed in 14 case-parent trios/quattros with clinical exclusion of PCD prior to analysis. Moreover, all cases and parents underwent detailed clinical phenotyping including physical examination, echocardiography by a skilled paediatric cardiologist and abdominal ultrasound examinations not to miss mildly affected individuals. Subsequent survey of the exome data comprised filtering for monoallelic de novo, rare biallelic, and X-linked recessive variants. In two families, rare variants of uncertain significance (VUS) in PKD1L1 and ZIC3 were identified. Both genes have been associated with laterality defects. In two of the remaining families, biallelic variants in LMBRD1 and DNAH17, respectively, were prioritized. In another family, an ultra-rare de novo variant in WDR47 was found. Extensive exome survey of 2,109 single exomes of individuals with situs inversus totalis, heterotaxy, or isolated CHD identified two individuals with novel monoallelic variants in WDR47, but no further individuals with biallelic variants in DNAH17 or LMBRD1. Overall, ES of 14 case-parent trios/quattros with cardiovascular laterality defects identified rare VUS in two families in known disease-associated genes PKD1L1 and ZIC3 and suggests DNAH17, LMBRD1, and WDR47 as potential genes involved in laterality defects.
CRIS-Team WoS Importer:2022-05-13

Exome Survey and Candidate Gene Re-Sequencing Identifies Novel Exstrophy Candidate Genes and Implicates LZTR1 in Disease Formation - Köllges, Ricarda; Stegmann, Jil; Schneider, Sophia; Waffenschmidt, Lea; Fazaal, Julia; Breuer, Katinka; Hilger, Alina Christine; Dworschak, Gabriel C.; Mingardo, Enrico; Rösch, Wolfgang; Hofmann, Aybike; Neissner, Claudia; et al. (Biomolecules, 2023)
Background: The bladder exstrophy-epispadias complex (BEEC) is a spectrum of congenital abnormalities that involves the abdominal wall, the bony pelvis, the urinary tract, the external genitalia, and, in severe cases, the gastrointestinal tract as well. Methods: Herein, we performed an exome analysis of case-parent trios with cloacal exstrophy (CE), the most severe form of the BEEC. Furthermore, we surveyed the exome of a sib-pair presenting with classic bladder exstrophy (CBE) and epispadias (E) only. Moreover, we performed large-scale re-sequencing of CBE individuals for novel candidate genes that were derived from the current exome analysis, as well as for previously reported candidate genes within the CBE phenocritical region, 22q11.2. Results: The exome survey in the CE case-parent trios identified two candidate genes harboring de novo variants (NR1H2, GKAP1), four candidate genes with autosomal-recessive biallelic variants (AKR1B10, CLSTN3, NDST4, PLEKHB1) and one candidate gene with suggestive uniparental disomy (SVEP1). However, re-sequencing did not identify any additional variant carriers in these candidate genes. Analysis of the affected sib-pair revealed no candidate gene. Re-sequencing of the genes within the 22q11.2 CBE phenocritical region identified two highly conserved frameshift variants that led to early termination in two independent CBE males, in LZTR1 (c.978_985del, p.Ser327fster6) and in SLC7A4 (c.1087delC, p.Arg363fster68). Conclusions: According to previous studies, our study further implicates LZTR1 in CBE formation. Exome analysis-derived candidate genes from CE individuals may not represent a frequent indicator for other BEEC phenotypes and warrant molecular analysis before their involvement in disease formation can be assumed.
CRIS-Team Scopus Importer:2023-08-11
Keywords: cloacal exstrophy; exome analysis; exstrophy; molecular inversion probe

Exome survey of individuals affected by VATER/VACTERL with renal phenotypes identifies phenocopies and novel candidate genes - Kolvenbach, Caroline M.; Van Der Ven, Amelie T.; Kause, Franziska; Shril, Shirlee; Scala, Marcello; Connaughton, Dervla M.; Mann, Nina; Nakayama, Makiko; Dai, Rufeng; Kitzler, Thomas M.; Schneider, Ronen; Schierbaum, Luca; et al. (American Journal of Medical Genetics Part A, 2021)
The acronym VATER/VACTERL refers to the rare nonrandom association of the following component features (CFs): vertebral defects (V), anorectal malformations (ARM) (A), cardiac anomalies (C), tracheoesophageal fistula with or without esophageal atresia (TE), renal malformations (R), and limb anomalies (L). For the clinical diagnosis, the presence of at least three CFs is required, individuals presenting with only two CFs have been categorized as VATER/VACTERL-like. The majority of VATER/VACTERL individuals displays a renal phenotype. Hitherto, variants in FGF8, FOXF1, HOXD13, LPP, TRAP1, PTEN, and ZIC3 have been associated with the VATER/VACTERL association; however, large-scale re-sequencing could only confirm TRAP1 and ZIC3 as VATER/VACTERL disease genes, both associated with a renal phenotype. In this study, we performed exome sequencing in 21 individuals and their families with a renal VATER/VACTERL or VATER/VACTERL-like phenotype to identify potentially novel genetic causes. Exome analysis identified biallelic and X-chromosomal hemizygous potentially pathogenic variants in six individuals (29%) in B9D1, FREM1, ZNF157, SP8, ACOT9, and TTLL11, respectively. The online tool GeneMatcher revealed another individual with a variant in ZNF157. Our study suggests six biallelic and X-chromosomal hemizygous VATER/VACTERL disease genes implicating all six genes in the expression of human renal malformations.
CRIS-Team Scopus Importer:2021-08-13
Keywords: anorectal malformation (ARM); congenital anomalies of the kidneys and urinary tract (CAKUT); exome sequencing (WES); monogenic disease causation; VATER/VACTERL association

Extracorporeal membrane oxygenation support in a newborn with lower urinary tract obstruction and pulmonary hypoplasia: A case report - Gatzweiler, Eva; Hoppe, Bernd; Berg, Christoph; Müller, Andreas; Reutter, Heiko Martin; Kipfmueller, Florian; Dewald, Oliver (Journal of Medical Case Reports, 2018)
Background: Survival of neonates with intrauterine renal insufficiency and oligo- or anhydramnios correlates with the severity of secondary pulmonary hypoplasia. Early prenatal diagnosis together with repetitive amnioinfusions and modern intensive care treatment have improved the prognosis of these neonates. Extracorporeal membrane oxygenation is an established treatment option, mainly applied to neonates with pulmonary hypoplasia caused by congenital diaphragmatic hernia. However, a few case reports of extracorporeal membrane oxygenation in neonates with lower urinary tract obstruction have been published. Case presentation: We describe a case of a Caucasian male infant with prenatally diagnosed lower urinary tract obstruction and secondary pulmonary hypoplasia who was delivered spontaneously at 36 + 2 weeks of gestation. Venovenous extracorporeal membrane oxygenation was initiated on the first day of life for severe respiratory failure and consecutive hypoxemia despite treatment with inhaled nitric oxide and high-frequency oscillation. The patient was supported by extracorporeal membrane oxygenation for 10 days and extubated 6 weeks later. Hemofiltration was required on the second day of life because of renal insufficiency and was later replaced by peritoneal dialysis. The child was discharged after 4 months with nasal high-flow mild oxygen therapy and peritoneal dialysis. Conclusion: Neonatal extracorporeal membrane oxygenation support is a possible treatment option for neonates with lower urinary tract obstruction and pulmonary hypoplasia.
CRIS-Team Scopus Importer:2022-05-03
Keywords: ECMO; Hemofiltration; LUTO; Peritoneal dialysis; Pulmonary hypoplasia

EZH2 specifically regulates ISL1 during embryonic urinary tract formation - Mingardo, Enrico; Kalanithy, Jeshurun C.; Dworschak, Gabriel; Ishorst, Nina; Yilmaz, Öznur; Lindenberg, Tobias; Hollstein, Ronja; Felger, Tim; Angrand, Pierre-Olivier; Reutter, Heiko M.; Reutter, Heiko Martin; Odermatt, Benjamin (Scientific Reports, 2024)
Isl1 has been described as an embryonic master control gene expressed in the pericloacal mesenchyme. Deletion of Isl1 from the genital mesenchyme in mice leads to an ectopic urethral opening and epispadias-like phenotype. Using genome wide association methods, we identified ISL1 as the key susceptibility gene for classic bladder exstrophy (CBE), comprising epispadias and exstrophy of the urinary bladder. The most significant marker (rs6874700) identified in our recent GWAS meta-analysis achieved a p value of 1.48 × 10- 24 within the ISL1 region. In silico analysis of rs6874700 and all other genome-wide significant markers in Linkage Disequilibrium (LD) with rs6874700 (D' = 1.0; R2 > 0.90) revealed marker rs2303751 (p value 8.12 × 10- 20) as the marker with the highest regulatory effect predicted. Here, we describe a novel 1.2 kb intragenic promoter residing between 6.2 and 7.4 kb downstream of the ISL1 transcription starting site, which is located in the reverse DNA strand and harbors a binding site for EZH2 at the exact region of marker rs2303751. We show, that EZH2 silencing in HEK cells reduces ISL1 expression. We show that ezh2-/- knockout (KO) zebrafish larvae display tissues specificity of ISL1 regulation with reduced expression of Isl1 in the pronephric region of zebrafish larvae. In addition, a shorter and malformed nephric duct is observed in ezh2-/- ko zebrafish Tg(wt1ß:eGFP) reporter lines. Our study shows, that Ezh2 is a key regulator of Isl1 during urinary tract formation and suggests tissue specific ISL1 dysregulation as an underlying mechanism for CBE formation.
CRIS-Team Scopus Importer:2024-10-11
Keywords: Classic bladder exstrophy; EZH2; Gene regulation; HEK293; ISL1; Promoter; Zebrafish

Familial congenital lower urinary tract obstruction (LUTO) suggested by screening for lower urinary tract dysfunction in parents of patients: A descriptive study - Ebach, Fabian; Wagner, Pauline; Stein, Raimund; Dolscheid-Pommerich, Ramona; Reutter, Heiko Martin; Hilger, Alina Christine (Health Science Reports, 2024)
Background: Congenital lower urinary tract obstruction (LUTO) describes a heterogeneous group of congenital malformations. Posterior urethral valves (PUV) represent the most common entity. Familial occurrence has been described, suggestive of underlying genetic factors. LUTO can occur in various degrees of severity. In severe forms, oligohydramnios, pulmonary hypoplasia, and renal damage can occur resulting in high pre- and postnatal mortality. On the contrary, mild forms may become apparent through recurrent urinary tract infections. Such high phenotypic variability has been described even within the same family. Here, we systematically screened parents of affected children for symptoms of LUTO. Methods: The study population consisted of parents of LUTO patients. Fathers over 50 years of age were excluded, to avoid inclusion of male phenocopies due to early prostatic hypertrophy. Uroflowmetry, ultrasonography for residual urine and hydronephrosis, and laboratory examination of standard renal retention parameters were assessed, and a detailed patient history was taken, including the assessment of the International Prostate Symptom Score. Results: Twenty-nine of 42 LUTO families enrolled were found eligible for the present study. Of these, we identified five families in which the father had already been diagnosed with infravesical obstruction (17%). Of the remaining families, nine agreed to participate in our study. Of these nine families, eight families had a child affected with PUV and one family had a child with urethral stenosis. Here, we found two fathers and one mother with symptoms of LUTO suggestive of mild LUTO and one family, in which the unborn male fetal brother of the affected index patient was also diagnosed prenatally with LUTO. Conclusion: Our observations suggest that LUTOs have a higher heritability than previously thought and that first-degree relatives of the affected should be clinically assessed for symptoms of LUTO.
CRIS-Team Scopus Importer:2024-04-05
Keywords: familial LUTO; IPSS; LUTO; obstructive uropathy; postvoid residual volume; PUV; uroflowmetry

First genome-wide association study of esophageal atresia identifies three genetic risk loci at CTNNA3, FOXF1/FOXC2/FOXL1, and HNF1B - Gehlen, Jan; Giel, Ann Sophie; Köllges, Ricarda; Haas, Stephan L.; Zhang, Rong; Trcka, Jiri; Sungur, Ayse; Renziehausen, Florian; Bornholdt, Dorothea; Jung, Daphne; Hoyer, Paul D.; Nordenskjöld, Agneta; et al. (Human Genetics and Genomics Advances, 2022)
Esophageal atresia with or without tracheoesophageal fistula (EA/TEF) is the most common congenital malformation of the upper digestive tract. This study represents the first genome-wide association study (GWAS) to identify risk loci for EA/TEF. We used a European case-control sample comprising 764 EA/TEF patients and 5,778 controls and observed genome-wide significant associations at three loci. On chromosome 10q21 within the gene CTNNA3 (p = 2.11 × 10−8; odds ratio [OR] = 3.94; 95% confidence interval [CI], 3.10–5.00), on chromosome 16q24 next to the FOX gene cluster (p = 2.25 × 10−10; OR = 1.47; 95% CI, 1.38–1.55) and on chromosome 17q12 next to the gene HNF1B (p = 3.35 × 10−16; OR = 1.75; 95% CI, 1.64–1.87). We next carried out an esophageal/tracheal transcriptome profiling in rat embryos at four selected embryonic time points. Based on these data and on already published data, the implicated genes at all three GWAS loci are promising candidates for EA/TEF development. We also analyzed the genetic EA/TEF architecture beyond the single marker level, which revealed an estimated single-nucleotide polymorphism (SNP)-based heritability of around 37% ± 14% standard deviation. In addition, we examined the polygenicity of EA/TEF and found that EA/TEF is less polygenic than other complex genetic diseases. In conclusion, the results of our study contribute to a better understanding on the underlying genetic architecture of ET/TEF with the identification of three risk loci and candidate genes.
CRIS-Team Scopus Importer:2022-03-04
Keywords: CTNNA3; esophageal atresia (EA); FOXF1/FOXC2/FOXL1; genome-wide association study (GWAS); HNF1B; multifactorial diseases

First postnatal lactate blood levels on day 1 and outcome of preterm infants with gestational age <29 weeks - Zipf, Stephanie; Fortmann, Ingmar; Härtel, Christoph; Andres, Oliver; Frieauff, Eric; Paul, Pia; Häfke, Anna; Reutter, Heiko Martin; Morhart, Patrick; Weller, Ursula; Welp, Amrei; Kipke, Henry; et al. (Frontiers in Pediatrics, 2024)
Background: Serum lactate levels are used as biomarkers for perinatal asphyxia, while their value for outcome prediction in preterm infants is uncertain. It was the aim of this observational study to determine the association of the first postnatal serum-lactate levels on day 1 of life and short-term outcome in preterm infants less than 29 gestational weeks. Methods: We analysed data in a population-based cohort of German Neonatal Network (GNN) preterm infants with available first postnatal lactate levels enrolled at 22–28 weeks of gestational age (GA) between 1st of April 2009 and 31st December 2020. We hypothesized that high lactate levels as measured in mmol/L increase the risk of intraventricular haemorrhage (IVH) and bronchopulmonary dysplasia (BPD) in infants with VLBW regardless of small-for-gestational-age (SGA) status. Hypotheses were evaluated in univariate analyses and multiple logistic regression models. Results: First postnatal lactate levels were available in 2499 infants. The study population had a median GA of 26.7 [IQR 25.2–27.9] weeks and birth weight of 840 g [IQR 665–995]. Infants with short-term complications such as IVH and BPD had higher initial lactate levels than non-affected infants. The positive predictive value of a lactate cut-off of 4 mmol/L was 0.28 for IVH and 0.30 for BPD. After adjustment for known confounding variables, each 1 mmol/L increase of day 1 lactate levels was associated with a modestly increased risk of IVH (OR 1.18; 95% CI 1.03–1.37; p = 0.002) and BPD (OR 1.23; 95% CI 1.06–1.43; p = 0.005) but not with sepsis or mortality. Notably, SGA was associated with lower risk of any grade and severe IVH (OR 0.70; 95% CI 0.54–0.85; p = 0.001). Conclusions: In our observational cohort study higher initial lactate levels were associated with adverse outcome regardless of SGA status. However, the predictive value of lactate cut-off levels such as 4 mmol/L is low.
CRIS-Team Scopus Importer:2024-11-01
Keywords: all-cause mortality; bronchopulmonary dysplasia; extremely preterm infants; intraventricular haemorrhage; lactate levels; small for gestational age

Genetic Counseling for Birth Defects - Reutter, Heiko Martin (European Journal of Pediatric Surgery, 2021)
CRIS-Team WoS Importer:2021-12-31

Genetic Counseling for Bladder Exstrophy-Epispadias Complex - Reutter, Heiko Martin; Holmdahl, Gundela (European Journal of Pediatric Surgery, 2021)
Bladder exstrophy-epispadias complex (BEEC) represents the severe end of the uro-rectal malformation spectrum and has profound impact on continence, sexual, and renal function. Treatment of BEEC is primarily surgical, and the main goals are safe closure of the abdominal wall, urinary continence while preserving renal function, and adequate cosmetic and functional genital reconstruction. Psychosocial and psychosexual outcomes and adequate health-related quality of life depend on long-term multidisciplinary care. The overall outcome is now considered very positive and affected individuals usually lead self-determined and independent lives with the desire to start their own families later in life. Certainty about the risk of recurrence and the provision of information about the current state of knowledge about the identified genetic causes with high penetrance will have an impact on family planning for healthy parents with an affected child and for affected individuals themselves. This review addresses this information and presents the current state of knowledge.
CRIS-Team WoS Importer:2021-12-31

GENOME-WIDE ASSOCIATION STUDY IN PATIENTS WITH ANATOMICAL OBSTRUCTIONS OF THE LOWER URINARY TRACT - Van Der Zanden, Loes F. M.; Maj, Carlo; Borisov, Oleg; Van Rooij, Iris A. L. M.; Quaedackers, Josine S. L. T.; Steffens, Martijn; Schierbaum, Luca; Schneider, Sophia; Waffenschmidt, Lea; Kiemeney, Lambert A. L. M.; De Wall, Liesbeth; Heilmann, Stefanie; et al. (PEDIATRIC NEPHROLOGY, 2022)
CRIS-Team WoS Importer:2022-09-30

Genome-wide association study in patients with posterior urethral valves - van der Zanden, Loes F.M.; Maj, Carlo; Borisov, Oleg; van Rooij, Iris A.L.M.; Quaedackers, Josine S.L.T.; Steffens, Martijn; Schierbaum, Luca; Schneider, Sophia; Waffenschmidt, Lea; Kiemeney, Lambertus A.L.M.; de Wall, Liesbeth L.L.; Heilmann, Stefanie; et al. (Frontiers in Pediatrics, 2022)
Congenital lower urinary tract obstructions (LUTO) are most often caused by posterior urethral valves (PUV), a male limited anatomical obstruction of the urethra affecting 1 in 4,000 male live births. Little is known about the genetic background of PUV. Here, we report the largest genome-wide association study (GWAS) for PUV in 4 cohorts of patients and controls. The final meta-analysis included 756 patients and 4,823 ethnicity matched controls and comprised 5,754,208 variants that were genotyped or imputed and passed quality control in all 4 cohorts. No genome-wide significant locus was identified, but 33 variants showed suggestive significance (P < 1 × 10−5). When considering only loci with multiple variants residing within < 10 kB of each other showing suggestive significance and with the same effect direction in all 4 cohorts, 3 loci comprising a total of 9 variants remained. These loci resided on chromosomes 13, 16, and 20. The present GWAS and meta-analysis is the largest genetic study on PUV performed to date. The fact that no genome-wide significant locus was identified, can be explained by lack of power or may indicate that common variants do not play a major role in the etiology of PUV. Nevertheless, future studies are warranted to replicate and validate the 3 loci that yielded suggestive associations.
CRIS-Team Scopus Importer:2022-10-28
Keywords: BMP7; genome wide association study; lower urinary tract obstruction; obstructive uropathy; PCDH9; posterior urethral valves; SALL1

Genome-wide identification of disease-causing copy number variations in 450 individuals with anorectal malformations - Fabian, Julia; Dworschak, Gabriel C.; Waffenschmidt, Lea; Schierbaum, Luca; Bendixen, Charlotte; Heilmann-Heimbach, Stefanie; Sivalingam, Sugirthan; Buness, Andreas; Schwarzer, Nicole; Boemers, Thomas M.; Schmiedeke, Eberhard; Neser, Jorg; et al. (European Journal of Human Genetics, 2022)
Anorectal malformations (ARM) represent a spectrum of rare malformations originating from a perturbated development of the embryonic hindgut. Approximately 60% occur as a part of a defined genetic syndrome or within the spectrum of additional congenital anomalies. Rare copy number variations (CNVs) have been associated with both syndromic and non-syndromic forms. The present study represents the largest study to date to explore the contribution of CNVs to the expression of ARMs. SNP-array-based molecular karyotyping was applied in 450 individuals with ARM and 4392 healthy controls. CNVs were identified from raw intensity data using PennCNV. Overlapping CNVs between cases and controls were discarded. Remaining CNVs were filtered using a stringent filter algorithm of nine filter steps. Prioritized CNVs were confirmed using qPCR. Filtering prioritized and qPCR confirmed four microscopic chromosomal anomalies and nine submicroscopic CNVs comprising seven microdeletions (del2p13.2, del4p16.2, del7q31.33, del9p24.1, del16q12.1, del18q32, del22q11.21) and two microduplications (dup2p13.2, dup17q12) in 14 individuals (12 singletons and one affected sib-pair). Within these CNVs, based on their embryonic expression data and function, we suggest FOXK2, LPP, and SALL3 as putative candidate genes. Overall, our CNV analysis identified putative microscopic and submicroscopic chromosomal rearrangements in 3% of cases. Functional characterization and re-sequencing of suggested candidate genes is warranted.
CRIS-Team Scopus Importer:2022-11-18

Genome-Wide Survey for Microdeletions or -Duplications in 155 Patients with Lower Urinary Tract Obstructions (LUTO) - Schierbaum, Luca M.; Schneider, Sophia; Herms, Stefan; Sivalingam, Sugirthan; Fabian, Julia; Reutter, Heiko Martin; Weber, Stefanie; Merz, Waltraut M.; Tkaczyk, Marcin; Miklaszewska, Monika; Sikora, Przemyslaw; Szmigielska, Agnieszka; et al. (Genes, 2021)
Lower urinary tract obstruction (LUTO) is, in most cases, caused by anatomical blockage of the bladder outlet. The most common form are posterior urethral valves (PUVs), a male-limited phenotype. Here, we surveyed the genome of 155 LUTO patients to identify disease-causing CNVs. Raw intensity data were collected for CNVs detected in LUTO patients and 4.392 healthy controls using CNVPartition, QuantiSNP and PennCNV. Overlapping CNVs between patients and controls were discarded. Additional filtering implicated CNV frequency in the database of genomic variants, gene content and final visual inspection detecting 37 ultra-rare CNVs. After, prioritization qPCR analysis confirmed 3 microduplications, all detected in PUV patients. One microduplication (5q23.2) occurred de novo in the two remaining microduplications found on chromosome 1p36.21 and 10q23.31. Parental DNA was not available for segregation analysis. All three duplications comprised 11 coding genes: four human specific lncRNA and one microRNA. Three coding genes (FBLIM1, SLC16A12, SNCAIP) and the microRNA MIR107 have previously been shown to be expressed in the developing urinary tract of mouse embryos. We propose that duplications, rare or de novo, contribute to PUV formation, a male-limited phenotype.
CRIS-Team WoS Importer:2021-10-08

High molecular diagnostic yields and novel phenotypic expansions involving syndromic anorectal malformations - Reutter, Heiko Martin (European Journal of Human Genetics, 2023)
CRIS-Team Scopus Importer:2023-01-13

Identification of de novo variants in nonsyndromic cleft lip with/without cleft palate patients with low polygenic risk scores - Ishorst, Nina; Henschel, Leonie; Thieme, Frederic; Drichel, Dmitriy; Sivalingam, Sugirthan; Mehrem, Sarah L.; Fechtner, Ariane C.; Fazaal, Julia; Welzenbach, Julia; Heimbach, André; Maj, Carlo; Borisov, Oleg; et al. (Molecular Genetics and Genomic Medicine, 2022)
Background: Nonsyndromic cleft lip with/without cleft palate (nsCL/P) is a congenital malformation of multifactorial etiology. Research has identified >40 genome-wide significant risk loci, which explain less than 40% of nsCL/P heritability. Studies show that some of the hidden heritability is explained by rare penetrant variants. Methods: To identify new candidate genes, we searched for highly penetrant de novo variants (DNVs) in 50 nsCL/P patient/parent-trios with a low polygenic risk for the phenotype (discovery). We prioritized DNV-carrying candidate genes from the discovery for resequencing in independent cohorts of 1010 nsCL/P patients of diverse ethnicities and 1574 population-matched controls (replication). Segregation analyses and rare variant association in the replication cohort, in combination with additional data (genome-wide association data, expression, protein–protein-interactions), were used for final prioritization. Conclusion: In the discovery step, 60 DNVs were identified in 60 genes, including a variant in the established nsCL/P risk gene CDH1. Re-sequencing of 32 prioritized genes led to the identification of 373 rare, likely pathogenic variants. Finally, MDN1 and PAXIP1 were prioritized as top candidates. Our findings demonstrate that DNV detection, including polygenic risk score analysis, is a powerful tool for identifying nsCL/P candidate genes, which can also be applied to other multifactorial congenital malformations.
CRIS-Team Scopus Importer:2022-12-23
Keywords: candidate genes; de novo variants; exome sequencing; nonsyndromic cleft lip with/without cleft palate; polygenic risk; single-molecule molecular inversion probes

Isolated cytokine-enriched pericardial effusion: A likely key feature for Aymé-Gripp syndrome - König, Anna Lina; Sabir, Hemmen; Strizek, Brigitte; Gembruch, Ulrich; Herberg, Ulrike; Bertrand, Miriam; Grasshoff, Ute; Wiegand, Gesa; Wiechers, Cornelia; Bernis, Eugenia; Reutter, Heiko Martin; Müller, Andreas (American Journal of Medical Genetics Part A, 2021)
Aymé-Gripp syndrome is a multisystemic disorder caused by a heterozygous variation in the MAF gene (OMIM*177075). Key features are congenital cataracts, sensorineural hearing loss, and a characteristic facial appearance. In a proportion of individuals, pericardial effusion or pericarditis has been reported as part of the phenotypic spectrum. In the present case, a large persistent cytokine-enriched pericardial effusion was the main pre- and postnatal symptom that led to the clinical and later molecular diagnosis of Aymé-Gripp syndrome. In the postnatal course, the typical Aymé-Gripp syndrome-associated features bilateral cataracts and hearing loss were diagnosed. We propose that activating dominant variants in the cytokine-modulating transcription factor c-MAF causes cytokine-enriched pericardial effusions possibly representing a key feature of Aymé-Gripp syndrome.
CRIS-Team Scopus Importer:2021-10-22
Keywords: Aymé-Gripp syndrome; congenital cataract; hearing loss; pericardial effusion

Loss of Function of GALNT2 Lowers High-Density Lipoproteins in Humans, Nonhuman Primates, and Rodents - Khetarpal, Sumeet A.; Schjoldager, Katrine T.; Christoffersen, Christina; Raghavan, Avanthi; Edmondson, Andrew C.; Reutter, Heiko M.; Ahmed, Bouhouche; Ouazzani, Reda; Peloso, Gina M.; Vitali, Cecilia; Zhao, Wei; Somasundara, Amritha Varshini Hanasoge; et al. (Cell Metabolism, 2016)
Human genetics studies have implicated GALNT2, encoding GalNAc-T2, as a regulator of high-density lipoprotein cholesterol (HDL-C) metabolism, but the mechanisms relating GALNT2 to HDL-C remain unclear. We investigated the impact of homozygous GALNT2 deficiency on HDL-C in humans and mammalian models. We identified two humans homozygous for loss-of-function mutations in GALNT2 who demonstrated low HDL-C. We also found that GALNT2 loss of function in mice, rats, and nonhuman primates decreased HDL-C. O-glycoproteomics studies of a human GALNT2-deficient subject validated ANGPTL3 and ApoC-III as GalNAc-T2 targets. Additional glycoproteomics in rodents identified targets influencing HDL-C, including phospholipid transfer protein (PLTP). GALNT2 deficiency reduced plasma PLTP activity in humans and rodents, and in mice this was rescued by reconstitution of hepatic Galnt2. We also found that GALNT2 GWAS SNPs associated with reduced HDL-C also correlate with lower hepatic GALNT2 expression. These results posit GALNT2 as a direct modulator of HDL metabolism across mammals.
EVALuna2:9336

Modelling human lower urinary tract malformations in zebrafish - Kolvenbach, Caroline M.; Dworschak, Gabriel C.; Rieke, Johanna M.; Woolf, Adrian S.; Reutter, Heiko Martin; Odermatt, Benjamin; Hilger, Alina Christine (Molecular and Cellular Pediatrics, 2023)
Advances in molecular biology are improving our understanding of the genetic causes underlying human congenital lower urinary tract (i.e., bladder and urethral) malformations. This has recently led to the identification of the first disease-causing variants in the gene BNC2 for isolated lower urinary tract anatomical obstruction (LUTO), and of WNT3 and SLC20A1 as genes implicated in the pathogenesis of the group of conditions called bladder-exstrophy-epispadias complex (BEEC). Implicating candidate genes from human genetic data requires evidence of their influence on lower urinary tract development and evidence of the found genetic variants’ pathogenicity. The zebrafish (Danio rerio) has many advantages for use as a vertebrate model organism for the lower urinary tract. Rapid reproduction with numerous offspring, comparable anatomical kidney and lower urinary tract homology, and easy genetic manipulability by Morpholino®-based knockdown or CRISPR/Cas editing are among its advantages. In addition, established marker staining for well-known molecules involved in urinary tract development using whole-mount in situ hybridization (WISH) and the usage of transgenic lines expressing fluorescent protein under a tissue-specific promoter allow easy visualization of phenotypic abnormalities of genetically modified zebrafish. Assays to examine the functionality of the excretory organs can also be modeled in vivo with the zebrafish. The approach of using these multiple techniques in zebrafish not only enables rapid and efficient investigation of candidate genes for lower urinary tract malformations derived from human data, but also cautiously allows transferability of causality from a non-mammalian vertebrate to humans.
CRIS-Team Scopus Importer:2023-04-14

"Multisystem Inflammatory Syndrome in Children"-Like Disease after COVID-19 Vaccination (MIS-V) with Potential Significance of Functional Active Autoantibodies Targeting G-Protein-Coupled Receptors (GPCR-fAAb) for Pathophysiology and Therapy. - Schmidt, Marius; Hébert, Steven; Wallukat, Gerd; Ponader, Rolf; Krickau, Tobias; Galiano, Matthias; Reutter, Heiko Martin; Wölfle, Joachim; Agaimy, Abbas; Mardin, Christian; Hörning, André; Hohberger, Bettina (Children, 2023)
BACKGROUND: An infection with SARS-CoV-2 can trigger a systemic disorder by pathological autoimmune processes. A certain type of this dysregulation is known as Multisystemic inflammatory syndrome in children (MIS-C). However, similar symptoms may occur and have been described as Multisystemic inflammatory syndrome after SARS-CoV-2 Vaccination (MIS-V) following vaccination against SARS-CoV-2. We report the case of a 12-year-old boy who was identified with MIS-C symptoms without previous SARS-CoV-2 infection after receiving two doses of the Pfizer-BioNTech COVID-19 vaccine approximately one month prior to the onset of symptoms. He showed polyserositis, severe gastrointestinal symptoms and, consequently, a manifestation of a multiorgan failure. IgG antibodies against spike proteins of SARS-CoV-2 were detected, indicating a successful vaccination, while SARS-CoV-2 Nucleocapsid protein antibodies and SARS-CoV-2 PCR were not detected. Several functional, active autoantibodies against G-protein-coupled receptors (GPCR-fAAb), previously associated with Long COVID disease, were detected in a cardiomyocyte bioassay. Immunosuppression with steroids was initiated. Due to side effects, treatment with steroids and later interleukin 1 receptor antagonists had to be terminated. Instead, immunoadsorption was performed and continued with tacrolimus and mycophenolic acid therapy, leading to improvement and discharge after 79 days. GPCR-fAAb decreased during therapy and remained negative after clinical curing and under continued immunosuppressive therapy with tacrolimus and mycophenolic acid. Follow-up of the patient showed him in good condition after one year. CONCLUSIONS: Infection with SARS-CoV-2 shows a broad and severe variety of symptoms, partly due to autoimmune dysregulation, which, in some instances, can lead to multiorgan failure. Despite its rarity, post-vaccine MIS-C-like disease may develop into a serious condition triggered by autoimmune dysregulation. The evidence of circulating GPCR-fAAb and their disappearance after therapy suggests a link of GPCR-fAAb to the clinical manifestations. Thus, we hypothesize a potential role of GPCR-fAAb in pathophysiology and their potential importance for the therapy of MIS-C or MIS-V. However, this observation needs further investigation to prove a causative correlation.
EVALuna2:547545

“Multisystem Inflammatory Syndrome in Children” (MIS-C) after COVID-19 Infection in the Metropolitan Area of Nuremberg-Erlangen, Germany—Expectations and Results of a Two-Year Period - Hébert, Steven; Schmidt, Marius; Topf, Georg; Rieger, Daniel; Klinge, Jens; Vermehren, Jan; Fusch, Christoph; Grillhösl, Christian; Schroth, Michael; Toni, Irmgard; Reutter, Heiko Martin; Morhart, Patrick; et al. (Children, 2023)
Background: Multisystemic Inflammatory Syndrome in children (MIS-C) is a rare autoimmune disorder occurring after a latency period following acute SARS-CoV-2 infection. The therapeutic regime of MIS-C is adapted to the therapy of the Kawasaki disease, as clinical symptoms are similar. Since the Kawasaki disease can potentially result in severe symptoms, which may even affect long-term health, it is essential to gain further knowledge about MIS-C. Thus, we aimed to investigate the incidence, symptoms, therapeutical procedure and outcome of MIS-C patients in the metropolitan area of Nuremberg-Erlangen during the SARS-CoV2 pandemic. Material and Methods: Retrospective analysis of clinical charts of MIS-C patients was carried out at three children’s hospitals covering the medical care of the metropolitan area of Nuremberg-Erlangen in Germany. Demographic characteristics and symptoms at first visit, their clinical course, therapeutic regime and outcome were recorded within the time period January 2021–December 2022. Results: Analysis of 10 patients (5 male, 5 female) with MIS-C resulting in an incidence of 2.14/100.000 children. The median time between COVID-19 infection and admission to hospital was 5 weeks. The median age was 7 years. Symptoms comprised fever (100%), rash (70%), bilateral non-purulent conjunctivitis (70%) and urticaria (20%). At the time of presentation, diagnosis-defining inflammation parameters were increased and the range for C-reactive protein was 4.13 mg/dL to 28 mg/dL, with a median of 24.7 mg/dL. Procalcitonin was initially determined in six patients (1.92 ng/mL to 21.5 ng/mL) with a median value of 5.5 pg/mL. Two patients displayed leukocytosis and two displayed leukopenia. None of the patients presented coronary pathologies. Nine of the ten patients received intravenous immunoglobulin (IVIG) therapy. In addition, patients received intravenous steroids (80%) and acetylsalicylic acid (80%). Conclusion: SARS-CoV virus may rarely exert multiorgan manifestations due to hyperinflammatory immunological processes. Within two years of the COVID-19 pandemic, we identified ten patients with COVID-induced MIS-C in the metropolitan area Nuremberg-Erlangen. In the description of the patient collective, we can confirm that MIS-C is distinguished from the Kawasaki disease by the lack of coronary manifestations. Interestingly, although having monitored all pediatric facilities in the investigated area, we find lower incidences of MIS-C compared to findings in the literature. In conclusion, an overestimation of incidences in the upcoming MIS-C during the pandemic needs to be considered.
CRIS-Team Scopus Importer:2023-09-08
Keywords: COVID-19; intravenous immunoglobulins; IVIG; mAbs; MIS-C; monoclonal antibodies; Multisystem Inflammatory Syndrome in children

Non-Syndromic and Syndromic Defects in Children with Extracranial Germ Cell Tumors: Data of 2610 Children Registered with the German MAKEI 96/MAHO 98 Registry Compared to the General Population - Schultewolter, Judit H.; Rissmann, Anke; von Schweinitz, Dietrich; Frühwald, Michael; Blattmann, Claudia; Fischer, Lars; Lange, Björn Sönke; Wessalowski, Rüdiger; Fröhlich, Birgit; Behnisch, Wolfgang; Schmid, Irene; Reinhard, Harald; et al. (Cancers, 2024)
GCTs are developmental tumors and are likely to reflect ontogenetic and teratogenetic determinants. The objective of this study was to identify syndromes with or without congenital anomalies and non-syndromic defects as potential risk factors. Patients with extracranial GCTs (eGCTs) registered in MAKEI 96/MAHO 98 between 1996 and 2017 were included. According to Teilum’s holistic concept, malignant and benign teratomas were registered. We used a case–control study design with Orphanet as a reference group for syndromic defects and the Mainz birth registry (EUROCAT) for congenital anomalies at birth. Co-occurring genetic syndromes and/or congenital anomalies were assessed accordingly. Odds ratios and 95% confidence intervals were calculated and p-values for Fisher’s exact test with Bonferroni correction if needed. A strong association was confirmed for Swyer (OR 338.6, 95% CI 43.7–2623.6) and Currarino syndrome (OR 34.2, 95% CI 13.2–88.6). We additionally found 16 isolated cases of eGCT with a wide range of syndromes. However, these were not found to be significantly associated following Bonferroni correction. Most of these cases pertained to girls. Regarding non-syndromic defects, no association with eGCTs could be identified. In our study, we confirmed a strong association for Swyer and Currarino syndromes with additional congenital anomalies.
CRIS-Team Scopus Importer:2024-06-21
Keywords: Currarino syndrome; developmental tumor; germ cell tumor; MAKEI 96/MAHO 98; non-syndromic defect; Swyer syndrome; syndrome

Nonurgent Visits to the Pediatric Emergency Department before and during the First Peak of the COVID-19 Pandemic - Guckert, Laura; Reutter, Heiko Martin; Saleh, Nadia; Ganschow, Rainer; Müller, Andreas; Ebach, Fabian (International Journal of Pediatrics, 2022)
Background. Nonurgent visits in pediatric Emergency Departments are a growing burden. In order to find predictors for those nonurgent visits, we performed a retrospective analysis of unscheduled visits at the Pediatric Emergency Department of the University Hospital of Bonn, Germany, in the year 2017. Additionally, we compared these findings to unscheduled visits during the first peak of the worldwide pandemic of the Coronavirus disease 2019, to see if there would be an effect on nonurgent pediatric Emergency Department attendances. Methods. For our retrospective cohort study, we analyzed more than 5.000 visits at the pediatric Emergency Department of the University Hospital of Bonn, Germany, before and during the first peak of the ongoing worldwide pandemic of the Coronavirus disease 2019, particularly with regard to their urgency. Data included gender, age, zip code, urgency, and preexisting conditions. Results. Our study shows that more than half of unscheduled pediatric Emergency Department visits (69%) at the University Hospital in Bonn are for nonurgent reasons, with short living distance being a factor to present children to a pediatric Emergency Department, even with minor complaints. During the first peak of the pandemic of the Coronavirus disease 2019, nonurgent visits decreased significantly, potentially due to hesitation to attend a pediatric Emergency Department with minor issues, fearing an infection with SARS-CoV-2 at the hospital. Conclusion. Many people use pediatric Emergency Departments for nonemergency complaints. In order to address the reasons for nonurgent visits to pediatric Emergency Departments and to prevent parents from doing so, further studies and targeted education concepts for parents are needed.
CRIS-Team Scopus Importer:2022-04-01

PKD1L1 Is Involved in Congenital Chylothorax - Whitchurch, Jonathan B.; Schneider, Sophia; Hilger, Alina Christine; Köllges, Ricarda; Stegmann, Jil D.; Waffenschmidt, Lea; Dyer, Laura; Thiele, Holger; Dhabhai, Bhanupriya; Dakal, Tikam Chand; Müller, Andreas; Norris, Dominic P.; et al. (Cells, 2024)
Besides visceral heterotaxia, Pkd1l1 null mouse embryos exhibit general edema and perinatal lethality. In humans, congenital chylothorax (CCT) is a frequent cause of fetal hydrops. In 2021, Correa and colleagues reported ultrarare compound heterozygous variants in PKD1L1 exhibiting in two consecutive fetuses with severe hydrops, implicating a direct role of PKD1L1 in fetal hydrops formation. Here, we performed an exome survey and identified ultrarare compound heterozygous variants in PKD1L1 in two of the five case-parent trios with CCT. In one family, the affected carried the ultrarare missense variants c.1543G>A(p.Gly515Arg) and c.3845T>A(p.Val1282Glu). In the other family, the affected carried the ultrarare loss-of-function variant (LoF) c.863delA(p.Asn288Thrfs*3) and the ultrarare missense variant c.6549G>T(p.Gln2183His). Investigation of the variants' impact on PKD1L1 protein localization suggests the missense variants cause protein dysfunction and the LoF variant causes protein mislocalization. Further analysis of Pkd1l1 mutant mouse embryos revealed about 20% of Pkd1l1-/- embryos display general edema and pleural effusion at 14.5 dpc. Immunofluorescence staining at 14.5 dpc in Pkd1l1-/- embryos displayed both normal and massively altered lymphatic vessel morphologies. Together, our studies suggest the implication of PKD1L1 in congenital lymphatic anomalies, including CCTs.
CRIS-Team Scopus Importer:2024-02-02
Keywords: chylothorax; congenital; PKD1L1; pleural effusion

Premature birth associated with a favorable course in gestational alloimmune liver disease (GALD): A case report - Mulzer, Linda-Marie; Reutter, Heiko Martin; Jüngert, Jörg M.; Knisely, A. S.; Schmid, Margit; Hörning, André; Morhart, Patrick (Frontiers in Pediatrics, 2023)
Gestational alloimmune liver disease (GALD) is a rare neonatal disorder with high mortality and morbidity. The patients come to caregivers' attention aged a few hours or days. The disease manifests as acute liver failure with or without siderosis. The differential diagnosis of neonatal acute liver failure (NALF) is broad, including mainly immunologic, infectious, metabolic and toxic disorders. The most common cause, however, is GALD followed by herpes simplex virus (HSV) infection. The best suited pathophysiological paradigm of GALD is that of a maternofetal alloimmune disorder. State of the art treatment combines intravenously administered immunoglobulin (IVIG) with exchange transfusion (ET). We report an infant born at 35 + 2 weeks' gestation in whom GALD had a favorable course, of interest because premature birth in our patient may have exerted protective aspects and lessened morbidity in that intrauterine exposure to maternal complement-fixing antibodies was shortened. The diagnosis of GALD was challenging and difficult. We suggest a modified diagnostic algorithm combining clinical findings with histopathologic findings in liver and lip mucosa and, if available, on abdominal magnetic resonance imaging-study focusing on the liver, spleen, and pancreas. This diagnostic workup must be followed by ET and subsequent administration of IVIG without delay.
CRIS-Team WoS Importer:2023-04-14

Re-sequencing of candidate genes FOXF1, HSPA6, HAAO, and KYNU in 522 individuals with VATER/VACTERL, VACTER/VACTERL-like association, and isolated anorectal malformation - Thiem, Corina E.; Stegmann, Jil D.; Hilger, Alina C.; Waffenschmidt, Lea; Bendixen, Charlotte; Köllges, Ricarda; Schmiedeke, Eberhard; Schäfer, Frank Mattias; Lacher, Martin; Kosch, Ferdinand; Grasshoff-Derr, Sabine; Kabs, Carmen; et al. (Birth Defects Research, 2022)
Background: The acronym VATER/VACTERL association describes the combination of at least three component features (CFs): vertebral defects (V), anorectal malformations (ARM) (A), cardiac defects (C), tracheoesophageal fistula with or without esophageal atresia (TE), renal malformations (R), and limb defects (L). Individuals presenting two CFs have been termed VATER/VACTERL-like. Recently, FOXF1, HSPA6, HAAO, KYNU, TRAP1, and ZIC3 have been proposed as candidate genes for VATER/VACTERL, VATER/VACTERL-like, and ARM. Re-sequencing studies identified disease-causing variants in TRAP1 and ZIC3, the contribution of other genes was not independently investigated. One affected variant carrier in FOXF1 was previously identified. Here we re-sequenced FOXF1, HSPA6, HAAO, and KYNU in 522 affected individuals. Methods: Using molecular inversion probe (MIP) technology, re-sequencing was performed in 63 individuals with VATER/VACTERL association, 313 with VATER/VACTERL-like association, and 146 with ARM. All individuals were of European ethnicity. Variant filtering considered variants with a minor allele frequency (MAF) ≤0.01 for putative recessive disease-genes HSPA6, HAAO, and KYNU. For the putative dominant disease-gene FOXF1 we considered variants with a MAF ≤0.0001. In silico prediction tools were used for further prioritization. Results: Only two variants in FOXF1 in two independently affected individuals [c.443G>T, p.(Cys148Phe); c.850T>C, p.(Tyr284His)] passed our filter criteria. One individual presented with ARM, the second presented with TE and C comprising atrial and ventricular septal defects. Sanger sequencing confirmed both variants but also their inheritance from the healthy mother. Conclusion: Our analysis suggests that FOXF1, HSPA6, HAAO and KYNU do not play a major role in the formation of VACTER/VACTERL phenotypes or ARM.
CRIS-Team Scopus Importer:2022-04-15
Keywords: anorectal malformation; birth defects; candidate gene; penetrance; variants

Resequencing of VEGFR3 pathway genes implicate GJC2 and FLT4 in the formation of primary congenital chylothorax - Schneider, Sophia; Kollges, Ricarda; Stegmann, Jil D.; Thieme, Frederic; Hilger, Alina C.; Waffenschmidt, Lea; Fazaal, Julia; Kalanithy, Jeshurun C.; Geipel, Annegret; Strizek, Brigitte; Ludwig, Kerstin U.; Reutter, Heiko Martin; et al. (American Journal of Medical Genetics Part A, 2022)
CRIS-Team WoS Importer:2022-01-14

SARS-CoV-2-Infektion in der Schwangerschaft und Auftreten von angeborenen Fehlbildungen – Besteht ein Zusammenhang? Auswertung von 8032 Schwangerschaften aus dem CRONOS-Register - Hofbauer, Anna; Schneider, Holm; Kehl, Sven; Reutter, Heiko Martin; Pecks, Ulrich; Andresen, Kristin; Morhart, Patrick (Zeitschrift für Geburtshilfe und Neonatologie, 2024)
Background Based on single case reports, the COVID-19 Related Obstetric and Neonatal Outcome Study (CRONOS) registry, sponsored by the German Society for Perinatal Medicine (DGPM), investigated the likelihood that SARS-CoV-2 infections of the mother in (early) pregnancy cause embryopathies and/or fetopathies. Material/Methods The CRONOS registry enrolled a total of 8032 women with confirmed SARS-CoV-2 infection during pregnancy at more than 130 participating hospitals from April 2020 to February 2023. Both maternal and fetal data were documented and the anonymized multicenter data were analyzed. Results Of 7142 fully documented pregnancies (including postnatal data), 140 showed congenital malformations. 8.57% of the mothers had had a SARS-CoV-2-infection in the 1st trimester and 36.43% in the 2nd trimester. In 66 cases with congenital malformations (47.14%), the malformation was only detected after the diagnosis of a maternal SARS-CoV-2 infection. The overall prevalence of congenital malformations in this cohort was 1.96%, compared to a prevalence of 2.39% reported in the EUROCAT (European network of population-based registries for the epidemiological surveillance of congenital anomalies) pre-pandemic registry between 2017-2019. Discussion Our multicenter data argue against a link between maternal SARS-CoV-2 infection in early pregnancy and congenital malformation.
CRIS-Team Scopus Importer:2024-02-23
Keywords: Coronavirus; COVID-19; CRONOS-registry; embryopathy; fetopathy; malformations

SIADH as a Rare Complication of Foramen Magnum Stenosis in an Infant With Achondroplasia. - Cebeci, Ayse Nurcan; Hébert, Steven; Reutter, Heiko Martin; Rompel, Oliver; Wölfle, Joachim (JCEM Case Reports, 2024)
Achondroplasia is the most common skeletal dysplasia and is associated with serious complications such as foramen magnum stenosis (FMS). This case report describes an infant with achondroplasia who presented with a syndrome of inappropriate antidiuretic hormone secretion (SIADH), secondary to significant FMS and myelocompression. A 2-month-old boy with prenatally diagnosed achondroplasia was referred due to disordered breathing and altered consciousness. On admission, apathy, hypotonus, and hypothermia with typical features of achondroplasia were noticed. Laboratory investigations revealed severe hyponatremia and hypochloridaemia with normal glucose and urea levels. The diagnosis of SIADH was made based on low serum osmolality in the presence of high urine osmolality, along with an elevated copeptin level. An emergency computerized tomography showed a high-grade stenosis at the cranio-cervical junction; subsequent magnetic resonance imaging demonstrated myelocompression. The patient underwent decompression surgery the next day; serum osmolality increased after the operation. Spontaneous breathing after extubation was sufficient whereas tetraplegia persisted despite intensive physiotherapy. Clinicians should be aware of SIADH as a presenting sign of FMS in children with achondroplasia. Further discussion is warranted regarding improving parental education and timing of screening recommendations.
EVALuna2:582017

SIADH as presenting feature of foramen magnum stenosis in a 2-month-old infant with achondroplasia (ACH): case report and discussion on management of infants with ACH in order to reduce the risk of serious complications - Cebeci, Ayse Nurcan; Hébert, Steven; Reutter, Heiko Martin; Wölfle, Joachim (HORMONE RESEARCH IN PAEDIATRICS, 2022)
CRIS-Team WoS Importer:2022-10-07

SLC20A1 Is Involved in Urinary Tract and Urorectal Development - Rieke, Johanna Magdalena; Zhang, Rong; Braun, Doreen; Yilmaz, Öznur; Japp, Anna S.; Lopes, Filipa M.; Pleschka, Michael; Hilger, Alina C.; Schneider, Sophia; Newman, William G.; Beaman, Glenda M.; Nordenskjöld, Agneta; et al. (Frontiers in Cell and Developmental Biology, 2020)
Previous studies in developing Xenopus and zebrafish reported that the phosphate transporter slc20a1a is expressed in pronephric kidneys. The recent identification of SLC20A1 as a monoallelic candidate gene for cloacal exstrophy further suggests its involvement in the urinary tract and urorectal development. However, little is known of the functional role of SLC20A1 in urinary tract development. Here, we investigated this using morpholino oligonucleotide knockdown of the zebrafish ortholog slc20a1a. This caused kidney cysts and malformations of the cloaca. Moreover, in morphants we demonstrated dysfunctional voiding and hindgut opening defects mimicking imperforate anus in human cloacal exstrophy. Furthermore, we performed immunohistochemistry of an unaffected 6-week-old human embryo and detected SLC20A1 in the urinary tract and the abdominal midline, structures implicated in the pathogenesis of cloacal exstrophy. Additionally, we resequenced SLC20A1 in 690 individuals with bladder exstrophy-epispadias complex (BEEC) including 84 individuals with cloacal exstrophy. We identified two additional monoallelic de novo variants. One was identified in a case-parent trio with classic bladder exstrophy, and one additional novel de novo variant was detected in an affected mother who transmitted this variant to her affected son. To study the potential cellular impact of SLC20A1 variants, we expressed them in HEK293 cells. Here, phosphate transport was not compromised, suggesting that it is not a disease mechanism. However, there was a tendency for lower levels of cleaved caspase-3, perhaps implicating apoptosis pathways in the disease. Our results suggest SLC20A1 is involved in urinary tract and urorectal development and implicate SLC20A1 as a disease-gene for BEEC.
CRIS-Team Scopus Importer:2020-09-04
Keywords: bladder exstrophy-epispadias complex; CAKUT; cloacal malformation; functional genetics; kidney formation; SLC20A1; urinary tract development; zebrafish development

The components of arginine and methylarginine metabolism are indicative of altered kidney function in intrauterine growth-restricted neonates - Kleinebenne, Lina; Röhrig, Waldemar; Ebach, Fabian; Reutter, Heiko Martin; Pankraz, Alexander; Heuchel, Katharina Monika; Müller, Andreas; Hilger, Alina (Journal of Hypertension, 2024)
Background: Intrauterine fetal growth restriction (IUGR) affects up to 10% of all pregnancies. Severe IUGR is associated with impaired kidney development, reduced nephron endowment, and chronic kidney disease later in life. Currently, no early predictive biomarker exists for detecting altered kidney function in neonates with IUGR. Because nephrons produce key enzymes for the metabolism of arginine and methylarginine components, we quantified and compared the concentrations of arginine and methylarginine metabolites between IUGR and non-IUGR neonates to identify potential biomarkers for the early detection of altered kidney function in IUGR neonates. Methods: Seventy-one IUGR and 123 non IUGR neonates were examined. Serum and Urine samples were obtained between 30 h and 5 days of life and between 5 and 70 days of life. Serum concentrations of creatinine, urea, symmetric and asymmetric-dimethylarginine metabolites (SDGV, SDMA, ADGV, and ADMA), guanidino-2-oxo-caproic acid (GOCA), citrulline, homocitrulline, arginine, and homoarginine were quantified using LC-MS/MS and standard clinical laboratory methods. Datasets were compared by Mann - Whitney - Wilcoxon or Chi-square tests for continuous and discrete parameters. P values were corrected for multiple comparisons using the Bonferroni method. Results: After Bonferroni correction, we found that serum creatinine, urea, SDGV, ADGV, and GOCA levels were significantly lower in neonates with IUGR. Consequently, the ratios of SDGV/SDMA, ADGV/ADMA, and GOCA/homoarginine were significantly lower in IUGR neonates. Conclusion: Our study suggests that arginine and methylarginine are possible early biomarkers for detecting altered kidney function in IUGR neonates.
CRIS-Team Scopus Importer:2024-09-06
Keywords: ADMA; AGXT2; arginine metabolites; glomerular filtration rate; homoarginine; IUGR; kidney function; SDMA

The genomic architecture of bladder exstrophy epispadias complex - Beaman, Glenda M.; Cervellione, Raimondo M.; Keene, David; Reutter, Heiko Martin; Newman, William G. (Genes, 2021)
The bladder exstrophy–epispadias complex (BEEC) is an abdominal midline malformation comprising a spectrum of congenital genitourinary abnormalities of the abdominal wall, pelvis, urinary tract, genitalia, anus, and spine. The vast majority of BEEC cases are classified as non-syndromic and the etiology of this malformation is still unknown. This review presents the current knowledge on this multifactorial disorder, including phenotypic and anatomical characterization, epidemiology, proposed developmental mechanisms, existing animal models, and implicated genetic and environmental components.
CRIS-Team Scopus Importer:2021-08-13
Keywords: BEEC; Bladder exstrophy; Cloacal exstrophy; Epispadias

The role of de novo variants in formation of human anorectal malformations - Dworschak, Gabriel C.; van Rooij, Iris A.L.M.; Reutter, Heiko Martin (Genes, 2021)
Anorectal malformations (ARM) represent a rare birth defect of the hindgut that occur in approximately 1 in 3000 live births. Around 60% of ARM occur with associated anomalies including defined genetic syndromes and associations with chromosomal aberrations. The etiology of ARM is heterogeneous, with the individual environmental or genetic risk factors remaining unknown for the majority of cases. The occurrence of familial ARM and previous epidemiologic analysis suggest autosomal dominant inheritance in a substantial subset of ARM patients. The implicated mortality and reduced fecundity in patients with ARM would lead to allele loss. However, mutational de novo events among the affected individuals could compensate for the evolutionary pressure. With the implementation of exome sequencing, array-based molecular karyotyping and family-based rare variant analyses, the technologies are available to identify the respective factors. This review discusses the identification of disease-causing variants among individuals with ARM. It highlights the role of mutational de novo events.
CRIS-Team Scopus Importer:2021-09-10
Keywords: Anorectal malformation (ARM); Birth defect; Copy number variation (CNV); De novo; Fecundity; Heritability

The role of de novo variants in patients with congenital diaphragmatic hernia - Bendixen, Charlotte; Reutter, Heiko Martin (Genes, 2021)
The genetic etiology of congenital diaphragmatic hernia (CDH), a common and severe birth defect, is still incompletely understood. Chromosomal aneuploidies, copy number variations (CNVs), and variants in a large panel of CDH-associated genes, both de novo and inherited, have been described. Due to impaired reproductive fitness, especially of syndromic CDH patients, and still significant mortality rates, the contribution of de novo variants to the genetic background of CDH is assumed to be high. This assumption is supported by the relatively low recurrence rate among siblings. Advantages in high-throughput genome-wide genotyping and sequencing methods have recently facilitated the detection of de novo variants in CDH. This review gives an overview of the known de novo disease-causing variants in CDH patients.
CRIS-Team Scopus Importer:2021-10-01
Keywords: Congenital diaphragmatic hernia; De novo variants; Impaired reproductive fitness; Mortality

Treatment of Esophageal Atresia in Germany: Analysis of National Hospital Discharge Data From 2016 to 2022 - Ungruh, Max; Hubertus, Jochen; Widenmann, Anke; Kaufmann, Jost; Reutter, Heiko Martin; Busse, Reinhard; Wilms, Miriam; Nimptsch, Ulrike (Journal of Pediatric Surgery, 2024)
Background: Esophageal atresia (EA) is a complex malformation. Multidisciplinary management is necessary, with the operative repair being the most challenging step in the treatment algorithm. The complete care structure for children with EA in Germany has not been analyzed yet. Methods: In the observed period 2016–2022, inpatient EA cases were analyzed 1) during the hospital stay of birth, and 2) during the hospital stay of corrective surgery in patients aged up to 365 days, both based on national hospital discharge data. Patients’ comorbidities, hospital caseload, treatment characteristics (e.g. surgical approach) and outcome parameters were analyzed. Results: 1) 1190 newborn EA cases were treated in 260 hospitals during the perinatal period. 54% had at least one additional malformation, and 16% had a birthweight below 1500 g. In-hospital mortality was 8.4%. 2) 1475 corrective operations for EA were performed in 111 hospitals with a consistent median annual caseload of 2 (P25–P95 1–8) per hospital. At least one indicator for a complicated perioperative course was documented in 63.7% of cases. The use of bronchoscopy was coded in 50% of cases. Median ventilation time during the entire hospital stay was 176 h (P25–P95: 95–1759 h). Conclusions: Newborns with EA are complex and early postoperative complications are common. The care structure is decentralized, and there was no trend towards centralization in the observed period. The low documented use of bronchoscopy is noteworthy. Centralization of the highly complex and schedulable corrective surgery for EA is necessary to evaluate outcomes and might improve the quality of care and resource utilization. Category of the manuscript and type of study: original article, observational cross-sectional study, secondary data analysis.
CRIS-Team Scopus Importer:2024-10-11
Keywords: Caseload; Centralization; Esophageal atresia; Quality of care; Volume-outcome relationship

Treatment Strategies and Outcome of the Exstrophy–Epispadias Complex in Germany: Data From the German CURE-Net - Ebert, Anne Karoline; Zwink, Nadine; Reutter, Heiko Martin; Jenetzky, Ekkehart; Stein, Raimund; Hölscher, Alice C.; Lacher, Martin; Fortmann, Caroline; Obermayr, Florian; Fisch, Margit; Mortazawi, Kiarasch; Schmiedeke, Eberhard; et al. (Frontiers in Pediatrics, 2020)
Introduction: To evaluate the impact of reconstructive strategies and post-operative management on short- and long-term surgical outcome and complications of classical bladder exstrophy (CBE) patients' comprehensive data of the multicenter German-wide Network for Congenital Uro-Rectal malformations (CURE-Net) were analyzed. Methods: Descriptive analyses were performed between 34 prospectively collected CBE patients born since 2009, median 3 months old [interquartile range (IQR), 2–4 months], and 113 cross-sectional patients, median 12 years old (IQR, 6–21 years). Results: The majority of included individuals were males (67%). Sixty-eight percent of the prospectively observed and 53% of the cross-sectional patients were reconstructed using a staged approach (p = 0.17). Although prospectively observed patients were operated on at a younger age, the post-operative management did not significantly change in the years before and after 2009. Solely, in prospectively observed patients, peridural catheters were used significantly more often (p = 0.017). Blood transfusions were significantly more frequent in males (p = 0.002). Only half of all CBE individuals underwent inguinal hernia repair. Cross-sectional patients after single-stage reconstructions showed more direct post-operative complications such as upper urinary tract dilatations (p = 0.0021) or urinary tract infections (p = 0.023), but not more frequent renal function impairment compared to patients after the staged approach (p = 0.42). Continence outcomes were not significantly different between the concepts (p = 0.51). Self-reported continence data showed that the majority of the included CBE patients was intermittent or continuous incontinent. Furthermore, subsequent consecutive augmentations and catheterizable stomata did not significantly differ between the two operative approaches. Urinary diversions were only reported after the staged concept. Conclusions: In this German multicenter study, a trend toward the staged concept was observed. While single-stage approaches tended to have initially more complications such as renal dilatation or urinary tract infections, additional surgery such as augmentations and stomata appeared to be similar after staged and single-stage reconstructions in the long term.
CRIS-Team Scopus Importer:2020-06-16
Keywords: exstrophy–epispadias complex (EEC); operative outcome; outcome assessment; post-operative complications; single-stage approach; staged approach; treatment strategies

Trio Exome Sequencing in VACTERL Association - Ćomić, Jasmina; Tilch, Erik; Riedhammer, Korbinian M.; Brugger, Melanie; Brunet, Theresa; Eyring, Katharina; Vill, Katharina; Redler, Silke; Tasic, Velibor; Schmiedeke, Eberhard; Schäfer, Frank Mattias; Abazi-Emini, Nora; et al. (Kidney International Reports, 2025)
Introduction: Currently, there is only limited data on monogenic causes of vertebral defects, anorectal malformations, cardiac defects, esophageal atresia or tracheoesophageal fistula, renal malformations, and limb defects (VACTERL) association. The aim of this study was to extend the spectrum of disease-causing variants in known genes, to determine the diagnostic yield of monogenic causes, and to identify candidate genes and rare variants by applying comprehensive genetic testing or rare variant burden. Methods: The total cohort comprised 101 affected individuals and their parents. Trio exome sequencing was only performed in 96 individuals and their parents because of DNA quality reasons and case-control gene and pathway burden tests were calculated and evaluated by quantile-quantile plots, principal component analysis plots and family-based association test (FBAT). Results: In 5 of 96 individuals, disease-causing variants in known genes or loci were identified to be associated with the following 4 disorders: Kabuki syndrome, Sotos syndrome, MELAS syndrome, and deletion syndrome encompassing TWIST1. In 91 individuals, no disease-causing variants were found. FBAT showed 14 significant variants, 2 significant genes (LOC645752 and ZNF417), and 8 significant pathways. Conclusion: This study shows that most individuals with VACTERL association do not have known discrete genetic syndromes, implying that pathomechanisms or variants not identifiable by exome sequencing may exist requiring further investigation.
CRIS-Team Scopus Importer:2025-01-31
Keywords: burden test; exome sequencing; mitochondriopathy; VACTERL association; VACTERL-like phenotype; ZNF417

Ultrasound Localization Microscopy for the Assessment of Microvascular Circulation in Ischemic Perinatal Stroke - Regensburger, Adrian; Wachter, Felix; Denis, Louise; Mandelbaum, Henriette; Schey, Frauke; Bühler, Adrian; Siebenlist, Gregor; Schwarz, Simone; Schulz-Heise, Susanne; Rompel, Oliver; Trollmann, Regina; Wölfle, Joachim; et al. (Stroke, 2024)
CRIS-Team Scopus Importer:2024-11-15
Keywords: diagnostic imaging; microcirculation; neonate; stroke; ultrasound

Ultrasound Super-Resolution Imaging of Neonatal Cerebral Vascular Reorganization - Schwarz, Simone; Denis, Louise; Nedoschill, Emmanuel; Bühler, Adrian; Danko, Vera; Hilger, Alina; Brevis Nuñez, Francisco; Dürr, Nikola R.; Schlunz-Hendann, Martin; Brassel, Friedhelm; Felderhoff-Müser, Ursula; Reutter, Heiko Martin; et al. (Advanced Science, 2025)
During the first days of neonatal growth, the central nervous system (CNS) develops self-regulatory mechanisms to ensure constant cerebral perfusion. However, this vascular neogenesis takes place at a microscopic scale that cannot be observed with current clinical imaging techniques. Ultrasound localization microscopy (ULM) allows us to observe micro-vessels of the order of a few microns at depths of several centimeters. This can be done using conventional clinical ultrasound scanners and contrast sequences (CEUS). In this study, ULM is used to observe the human microvasculature in neonatal patients undergoing treatment for life-threatening malformations forming direct connections between the cerebral arterial and venous systems. It is observed that neuroendovascular treatment of neonatal arteriovenous malformations causes remodeling and reorganization of the cerebral vasculature by also activating corticomedullary vascular connections. ULM enables us to follow microvascular changes in human neonates with high spatio-temporal resolution. ULM may provide a novel clinical translatable tool, particularly including cerebral imaging in very young patients.
CRIS-Team Scopus Importer:2025-02-14
Keywords: CEUS; microbubbles; super-resolution imaging; ultrasound; ultrasound localization microscopy; Vein of Galen malformation

Umbilical venous catheter- and peripherally inserted central catheter-associated complications in preterm infants with birth weight < 1250 g: Results from a survey in Austria and Germany Nabelvenenkatheter- und periphere zentrale katheterassoziierte Komplikationen bei Frühgeborenen mit einem Geburtsgewicht < 1250 g: Ergebnisse einer Umfrage in Österreich und Deutschland - Hess, Steffi; Poryo, Martin; Boettger, Ralf; Franz, Axel; Klotz, Daniel; Linnemann, Knud; Ott, Torsten; Poeschl, Johannes; Schroth, Michael; Stein, Anja; Ralser, Elisabeth; Reutter, Heiko Martin; et al. (Wiener Medizinische Wochenschrift, 2022)
Background and objective: Umbilical venous catheters (UVC) and peripherally inserted central catheters (PICC) are commonly used in preterm infants but have been associated with a number of serious complications. We performed a survey in Austria and Germany to assess the use of UVCs and PICCs in preterm infants with a birth weight < 1250 g and associated rates of catheter-related adverse events. Methods: Electronic survey of participating centers of the NeoVitaA trial. Main outcome parameter was the reported rates of UVC- and PICC-associated complications (infection, thrombosis, emboli, organ injury, arrhythmia, dislocation, miscellaneous). Results: In total, 20 neonatal intensive care units (NICU) providing maximal intensive care in Austria and Germany (level I) were contacted, with a senior neonatologist response rate of 12/20 (60%). The reported rates for UVC with a dwell time of 1–10 days were bacterial infection: 4.2 ± 3.4% (range 0–10%); thrombosis: 7.3 ± 7.1% (0–20%); emboli: 0.9 ± 2.0% (0–5%); organ injury: 1.1 ± 1.9% (0–5%); cardiac arrhythmia: 2.2 ± 2.5% (0–5%); and dislocation: 5.4 ± 8.7% (0–30%); and for PICCs with a dwell time of 1–14 days bacterial infection: 15.0 ± 3.4% (range 2.5–30%); thrombosis; 4.3 ± 3.5% (0–10%); emboli: 0.8 ± 1.6% (0–5%); organ injury: 1.5 ± 2.3% (0–5%); cardiac arrhythmia: 1.5 ± 2.3% (0–5%), and dislocation: 8.5 ± 4.6% (0–30%). Conclusion: The catheter-related complication rates reported in this survey differed between UVCs and PICCs and were higher than those reported in the literature. To generate more reliable data on this clinically important issue, we plan to perform a large prospective multicenter randomized controlled trial investigating the non-inferiority of a prolonged UVC dwell time (up to 10 days) against the early change (up to 5 days) to a PICC.
CRIS-Team Scopus Importer:2022-08-19
Keywords: Emboli; Infection; Organ injury; Peripherally inserted central catheter; Survey; Thrombosis; Umbilical venous catheter; Very low birth weight infants

Unraveling the Genetics of Congenital Diaphragmatic Hernia: An Ongoing Challenge - Brosens, Erwin; Peters, Nina C.J.; van Weelden, Kim S.; Bendixen, Charlotte; Brouwer, Rutger W.W.; Sleutels, Frank; Bruggenwirth, Hennie T.; van Ijcken, Wilfred F.J.; Veenma, Danielle C.M.; Otter, Suzan C.M.Cochius Den; Wijnen, Rene M.H.; Eggink, Alex J.; et al. (Frontiers in Pediatrics, 2022)
Congenital diaphragmatic hernia (CDH) is a congenital structural anomaly in which the diaphragm has not developed properly. It may occur either as an isolated anomaly or with additional anomalies. It is thought to be a multifactorial disease in which genetic factors could either substantially contribute to or directly result in the developmental defect. Patients with aneuploidies, pathogenic variants or de novo Copy Number Variations (CNVs) impacting specific genes and loci develop CDH typically in the form of a monogenetic syndrome. These patients often have other associated anatomical malformations. In patients without a known monogenetic syndrome, an increased genetic burden of de novo coding variants contributes to disease development. In early years, genetic evaluation was based on karyotyping and SNP-array. Today, genomes are commonly analyzed with next generation sequencing (NGS) based approaches. While more potential pathogenic variants are being detected, analysis of the data presents a bottleneck—largely due to the lack of full appreciation of the functional consequence and/or relevance of the detected variant. The exact heritability of CDH is still unknown. Damaging de novo alterations are associated with the more severe and complex phenotypes and worse clinical outcome. Phenotypic, genetic—and likely mechanistic—variability hampers individual patient diagnosis, short and long-term morbidity prediction and subsequent care strategies. Detailed phenotyping, clinical follow-up at regular intervals and detailed registries are needed to find associations between long-term morbidity, genetic alterations, and clinical parameters. Since CDH is a relatively rare disorder with only a few recurrent changes large cohorts of patients are needed to identify genetic associations. Retrospective whole genome sequencing of historical patient cohorts using will yield valuable data from which today's patients and parents will profit Trio whole genome sequencing has an excellent potential for future re-analysis and data-sharing increasing the chance to provide a genetic diagnosis and predict clinical prognosis. In this review, we explore the pitfalls and challenges in the analysis and interpretation of genetic information, present what is currently known and what still needs further study, and propose strategies to reap the benefits of genetic screening.
CRIS-Team Scopus Importer:2022-02-25
Keywords: congenital; counseling; development; diaphragm; discordant monozygotic twin; foregut; genetics; hernia

Whole-exome sequencing identifies causative mutations in families with congenital anomalies of the kidney and urinary tract - Van Der Ven, Amelie T.; Connaughton, Dervla M.; Ityel, Hadas; Mann, Nina; Nakayama, Makiko; Chen, Jing; Vivante, Asaf; Hwang, Daw-Yang; Schulz, Julian; Braun, Daniela A.; Schmidt, Johanna Magdalena; Schapiro, David; et al. (Journal of the American Society of Nephrology, 2018)
Background Congenital anomalies of the kidney and urinary tract (CAKUT) are the most prevalent cause of kidney disease in the first three decades of life. Previous gene panel studies showed monogenic causation in up to 12% of patients with CAKUT. Methods We applied whole-exome sequencing to analyze the genotypes of individuals from 232 families with CAKUT, evaluating for mutations in single genes known to cause human CAKUT and genes known to cause CAKUT in mice. In consanguineous or multiplex families, we additionally performed a search for novel monogenic causes of CAKUT. Results In 29 families (13%), we detected a causative mutation in a known gene for isolated or syndromic CAKUT that sufficiently explained the patient's CAKUT phenotype. In three families (1%), we detected a mutation in a gene reported to cause a phenocopy of CAKUT. In 15 of 155 families with isolated CAKUT, we detected deleterious mutations in syndromic CAKUT genes. Our additional search for novel monogenic causes of CAKUT in consanguineous and multiplex families revealed a potential single, novel monogenic CAKUT gene in 19 of 232 families (8%). Conclusions We identified monogenic mutations in a known human CAKUT gene or CAKUT phenocopy gene as the cause of disease in 14% of the CAKUT families in this study. Whole-exome sequencing provides an etiologic diagnosis in a high fraction of patients with CAKUT and will provide a new basis for the mechanistic understanding of CAKUT.
Created from Fastlane, Scopus look-up

X-linked variations in SHROOM4 are implicated in congenital anomalies of the urinary tract and the anorectal, cardiovascular and central nervous systems - Kolvenbach, Caroline M.; Felger, Tim; Schierbaum, Luca; Thiffault, Isabelle; Pastinen, Tomi; Szczepanska, Maria; Zaniew, Marcin; Adamczyk, Piotr; Bayat, Allan; Yilmaz, Oeznur; Lindenberg, Tobias T.; Thiele, Holger; et al. (Journal of Medical Genetics, 2022)
BackgroundSHROOM4 is thought to play an important role in cytoskeletal modification and development of the early nervous system. Previously, single-nucleotide variants (SNVs) or copy number variations (CNVs) in SHROOM4 have been associated with the neurodevelopmental disorder Stocco dos Santos syndrome, but not with congenital anomalies of the urinary tract and the visceral or the cardiovascular system. MethodsHere, exome sequencing and CNV analyses besides expression studies in zebrafish and mouse and knockdown (KD) experiments using a splice blocking morpholino in zebrafish were performed to study the role of SHROOM4 during embryonic development. ResultsIn this study, we identified putative disease-causing SNVs and CNVs in SHROOM4 in six individuals from four families with congenital anomalies of the urinary tract and the anorectal, cardiovascular and central nervous systems (CNS). Embryonic mouse and zebrafish expression studies showed Shroom4 expression in the upper and lower urinary tract, the developing cloaca, the heart and the cerebral CNS. KD studies in zebrafish larvae revealed pronephric cysts, anomalies of the cloaca and the heart, decreased eye-to-head ratio and higher mortality compared with controls. These phenotypes could be rescued by co-injection of human wild-type SHROOM4 mRNA and morpholino. ConclusionThe identified SNVs and CNVs in affected individuals with congenital anomalies of the urinary tract, the anorectal, the cardiovascular and the central nervous systems, and subsequent embryonic mouse and zebrafish studies suggest SHROOM4 as a developmental gene for different organ systems.
CRIS-Team WoS Importer:2022-12-16